Hadith #2129 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
A woman who marries on a dower or a reward or a promise before the solemnisation of marriage is entitled to it; and whatever is fixed for her after solemnisation of marriage belongs to whom it is given. A man is more entitled to receive a thing given as a gift on account of his daughter or sister (than other kinds of gifts).
Grade: Hasan

Hadith #2132 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة (Sunan Abi Dawud)
A man called Basrah b. Akhtam married a woman. The narrator then reported the rest of the tradition to the same effect. This version added: And he separated them. The tradition narrated by Ibn Juraij is perfect.
Grade: Da'if

Hadith #2140 - Sunan Abi Dawud - Abu Hurairah; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
I went to al-Hirah and saw them (the people) prostrating themselves before a satrap of theirs, so I said: The Messenger of Allah (ﷺ) has most right to have prostration made before him. When I came to the Prophet (ﷺ), I said: I went to al-Hirah and saw them prostrating themselves before a satrap of theirs, but you have most right, Messenger of Allah, to have (people) prostrating themselves before you. He said: Tell me , if you were to pass my grave, would you prostrate yourself before it? I s
Grade: Sahih

Hadith #2151 - Sunan Abi Dawud - Abdullah bin Tawus عبد الله بن طاوس; Abu Hurairah; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
Jabir said “The Prophet (ﷺ) saw a woman so he entered upon Zainab daughter of Jahsh and had intercourse with her. He (ﷺ) then came out and said to his companions and said to them “A woman advances in the form of a devil. When one of you finds that he should go to his wife (and have intercourse with her) for that will repel what he is feeling.
Grade: Sahih

Hadith #2152 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
Ibn ‘Abbas said “I did not see anything more resembling to minor sins than what Abu Hurairah reported from the Prophet (ﷺ) who said “Allaah has decreed for the children of Adam a share in adultery, he will get it by all means, the adultery of eyes is looking; the adultery of tongue is speaking; the soul desires and has a passion; the private parts confirms or falsifies it.”
Grade: Sahih

Hadith #2153 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; al-Q'qa' bin Hkym al-Knany القعقاع بن حكيم الكناني المدني; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Abu Hurairah reported the Prophet (ﷺ) as saying “ Every child of Adam has his share in adultery. He then narrated the rest of the tradition. This version goes “And the hands commit adultery; their adultery is catching; and the legs commit adultery; their adultery is walking; and the mouth commits adultery – its adultery is kissing.”
Grade: Sahih

Hadith #2161 - Sunan Abi Dawud - Abu Hurairah; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
Ibn ‘Abbas reported the Prophet (ﷺ) as saying “If anyone who means to have intercourse with his wife says “In the name of Allaah, O Allaah, keep us away from the devil and keep the devil away from what You hast provided us.” It will be ordained that no devil will ever harm the child born to them.
Grade: Sahih

Hadith #2174 - Sunan Abi Dawud - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ammar bin Razayq عمار بن رزيق; Ikrama عكرمة; Yahya bin Y'amar يحيى بن يعمر; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
AbuNadrah reported: An old man of Tufawah said to me: I was a guest of AbuHurayrah at Medina. I did not find any one of the companions of the Prophet (ﷺ) more devoted to worship and more hospitable than AbuHurayrah. One day I was with him when he was sitting on his bed. He had a purse which contained pebbles or kernels. A black slave-girl of his was sitting below. Counting them he was glorifying Allah. When the pebbles or the kernels in the purse were finished, she gathered them and put them a
Grade: Da'if

Hadith #2175 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Prophet (ﷺ) said: Anyone who incites a woman against her husband or a slave against his master is not one of us.
Grade: Sahih

Hadith #2193 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Ata' bin Abi Rabah عطاء بن أبي رباح (Sunan Abi Dawud)
I went out with Adi ibn Adi al-Kindi till we came to Mecca. He sent me to Safiyyah daughter of Shaybah who remembered a tradition (that she had heard) from Aisha. She said: I heard Aisha say: I heard the Messenger of Allah (ﷺ) say: There is no divorce or emancipation in case of constraint or duress (ghalaq). Abu Dawud said: I think ghalaq means anger.
Grade: Hasan

Hadith #2203 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A’ishah said The Apostle of Allaah(ﷺ) gave us our choice and we chose him so that was not reckoned anything (i.e., divorce)
Grade: Sahih

Hadith #2208 - Sunan Abi Dawud - Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة; Zararah bin Awfa al-'Amiri al-Harshi زرارة بن أوفى العامري الحرشي (Sunan Abi Dawud)
What did you intend? He said: A single utterance of divorce. He said: Do you swear by Allah? He replied: I swear by Allah. He said: It stands as you intended. Abu Dawud said: This tradition is sounder than that of Ibn Juraij that Rukanah divorced his wife by three pronouncements, for they are the members of his family and they are more aware for him. The tradition of Ibn Juraij has been narrated by some children of Abu Rafi’ from ‘Ikrimah on the authority of Ibn ‘Abbas.
Grade: Da'if

Hadith #2211 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan Abi Dawud)
Abu Tamimah reported from a man of his tribe “The Prophet (ﷺ) heard a man say his wife “O my younger sister! So he prohibited him (addressing his wife in this manner) Abu Dawud said “This tradition has also been transmitted by ‘Abd Al Aziz bin Al Mukhtar from Khalid from Abu ‘Uthman from Abu Thamimah from the Prophet (ﷺ). This has also been narrated by Shu’bah from Khalid from a man on the authority of Abu Thamimah from the Prophet (ﷺ).
Grade: Da'if

Hadith #2259 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The words narrated by Malik alone are: “and he attributed the child to the woman.” Yunus narrated from Al Zuhri on the authority of Sahl bin Sa’d in the tradition regarding li’an(invoking curses). He disowned her conception hence her child was attributed to her.
Grade: Sahih

Hadith #2261 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The tradition mentioned above has also been narrated by Al Zuhri through a different chain of narrators to the same effect. This version adds “At that time he was hinting at disowning the child.”
Grade: Sahih

Hadith #2262 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Abi Sa'id; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
A bedouin came to the Prophet (ﷺ), and said: My wife has given birth to a black son, and I disown him. He then narrated the rest of the tradition to the same effect.
Grade: Sahih

Hadith #2323 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: The two months of ‘Id (festival), Ramadan and Dhu al-Hijjah, are not defective.
Grade: Sahih

Hadith #2334 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
AbuIshaq reported on the authority of Silah: We were with Ammar on the day when the appearance of the moon was doubtful. (The meat of) goat was brought to him. Some people kept aloof from (eating) it. Ammar said: He who keeps fast on this day disobeys AbulQasim (i.e. the Prophet) (ﷺ).
Grade: Sahih

Hadith #2336 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
She never saw the Prophet (ﷺ) fasting the whole month except Sha’ban which he combined with Ramadan.
Grade: Sahih

Hadith #2344 - Sunan Abi Dawud - Abu Hurairah; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) invited me to a meal shortly before dawn in Ramadan saying: Come to the blessed morning meal.
Grade: Sahih

Hadith #2349 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
When the verse “Until the white thread of dawn appear to you distinct from its black thread” was revealed, I took a white rope and a black rope, and placed them beneath my pillow ; and then I looked at them, byt they were not clear to me. So I mentioned it to the Messenger of Allah (ﷺ). He laughed and said: Your pillow is so broad and lengthy ; that is (i.e. means) night and day. The version of the narrator ‘Uthman has: That is the blackness of night and whiteness of day.
Grade: Sahih

Hadith #2352 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
We went along with the Messenger of Allah (ﷺ) while he was fasting. When the sun set, he said to Bilal: Bilal, come down and prepare barley beverage for us. He said: Messenger of Allah, would that you waited for the evening. He said: Come down and prepare barley beverage for us. He said: Messenger of Allah, the say still remains on you (i.e. there remains the brightness of the day). He said: Come down and prepare barley drink for us. So he came down and prepared barley drink. The Messenger of
Grade: Sahih

Hadith #2361 - Sunan Abi Dawud - Abu Hurairah; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not observe perpetual fasting. If any of you wants to observe perpetual fast, he should observe it until the dawn. They (the people) asked: You observe perpetual fast ? He replied: My position is not like that of yours. There is One Who gives me to eat, and there is One who gives me to drink.
Grade: Sahih

Hadith #2362 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone does not abandon falsehood and action is accordance with it, Allah has no need that he should abandon his food and drink. The narrator Ahmad (b. Yunus) said: I learnt the chain of narrators from Ibn Abi Dhi’b, and a man by his side made me understand the tradition. I think he was his cousin.
Grade: Sahih

Hadith #2379 - Sunan Abi Dawud - Abu Hurairah; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Ibn Sirin محمد بن سيرين الأنصاري; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
I did not see any of our companions who abominated the use of collyrium by a man who fasting. Ibrahim would permit the man who was fasting to apply collyrium with aloes.
Grade: Hasan

Hadith #2386 - Sunan Abi Dawud - Abu Hurairah; al-Aghr bin al-Sbah al-Tmymy الأغر بن الصباح التميمي المنقري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Abi Dawud)
The Prophet (ﷺ) used to kiss her and suck her tongue when he was fasting.
Grade: Da'if

Hadith #2389 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A man said to Messenger of Allah (ﷺ): Messenger of Allah, I was overtaken by dawn while I was sexually defiled, and I want to keep fast. The Messenger of Allah (ﷺ) said: I am also overtaken by dawn while I am in the state of sexual defilement ; I also want to keep fast. I take a bath and I keep fast. The man said: Messenger of Allah, you are not like us ; Allah has forgiven you your past and future sins. The Messenger of Allah (ﷺ) became angry and said: I swear by Allah, I hope I shall be
Grade: Sahih

Hadith #2391 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
This was a special concession for him. If a man commits this act today, the expiation is necessary for him. Abu Dawud said: Al-Laith b. Sa’d, al-Awza’i, Mansur b. al-Mu’tamir and ‘Irak b. Malik have narrated this tradition like the one narrated by Ibn ‘Uyainah. Al-Awza’i narrated in his version the words: Beg pardon of Allah.
Grade: Sahih

Hadith #2392 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك (Sunan Abi Dawud)
(A man broke his fast intentionally) during Ramadan. The Messenger of Allah (ﷺ) commanded him to emancipate a slave, or fast for two months, or feed sixty poor men. He said: I cannot provide. The Messenger of Allah (ﷺ) said: Sit down. Thereafter a huge basket of dates (‘araq) was brought to the Messenger of Allah (ﷺ). He said: Take this and give it as sadaqah (alms). He said: Messenger of Allah, there is no poorer than I. The Messenger of Allah (ﷺ) thereupon laughed so that his canine
Grade: Sahih

Hadith #2395 - Sunan Abi Dawud - Abu al-Matwas أبو المطوس; Abu Hurairah; Amarh bin 'Umayr al-Tymy عمارة بن عمير التيمي; Habib bin Abi Thabit حبيب بن أبي ثابت قيس; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
A huge basket containing twenty sa’s (of dates) was brought.
Grade: Hasan

Hadith #2396 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone breaks his fast one day in Ramadan without a concession granted to him by Allah, a perpetual fast will not atone for it.
Grade: Da'if

Hadith #2397 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Sufyan and Shu’bah differed among themselves on the name of the narrator Ibn al-Mutawwas and Abu al-Mutawwas.
Grade: Da'if

Hadith #2419 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Prophet (ﷺ) said: The day of Arafah, the day of sacrifice, the days of tashriq are (the days of) our festival, O people of Islam. These are the days of eating and drinking.
Grade: Sahih

Hadith #2428 - Sunan Abi Dawud - Abu Hurairah; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ja'far bin Iyas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The father or Uncle of Mujibah al-Bahiliyyah visited the Messenger of Allah (ﷺ). He then went away and came to him (again) after one year when his condition and appearance had changed. He said: Messenger of Allah, do you not recognize me? He asked: Who are you? He replied: I am al-Bahili who came to you last year. He said: What has changed you? You were looking well, then you were good in appearance? He said: I have only food at night since I departed from you. Thereupon the Messenger of Allah
Grade: Da'if

Hadith #2434 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to fast to such an extent that we thought that he would never break his fast, and he would go without fasting to such an extent that we thought he would never fast. I never saw the Messenger of Allah (ﷺ) fast a complete month except in Ramadan, and I never saw his fast more in any month than in Sha’ban.
Grade: Sahih

Hadith #2457 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
Some food was presented to me and Hafsah. We were fasting, but broke our fast. Then the Messenger of Allah (ﷺ) entered upon us. We said to him: A gift was presented to us; we coveted it and we broke our fast. The Messenger of Allah (ﷺ) said: There is no harm to you; keep a fast another day in lieu of it.
Grade: Da'if

Hadith #2459 - Sunan Abi Dawud - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; Abu Hurairah; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري (Sunan Abi Dawud)
A woman came to the Prophet (ﷺ) while we were with him. She said: Messenger of Allah, my husband, Safwan ibn al-Mu’attal, beats me when I pray, and makes me break my fast when I keep a fast, and he does not offer the dawn prayer until the sun rises. He asked Safwan, who was present, about what she had said. He replied: Messenger of Allah, as for her statement “he beats me when I pray”, she recites two surahs (during prayer) and I have prohibited her (to do so). He (the Prophet) said: If
Grade: Sahih

Hadith #2460 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
When one of you receives an invitation (for a meal), he should accept it. If he isn to fasting, he should eat, and if he is fasten, he should pray. Hisham said: The word salat means to pray (for him to Allah). Abu Dawud said: This tradition has also been narrated by Hafs b. Ghiyath from Hisham.
Grade: Sahih

Hadith #2465 - Sunan Abi Dawud - Abu Bakr As-Siddique; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
The Prophet (ﷺ) used to observe I’tikaf during the last ten days of Ramadan. Nafi’ said: ‘Abd Allah (b. ‘Umar) showed me the place in the mosque where Messenger of Allah (ﷺ) used to observe I’tikaf.
Grade: Sahih

Hadith #2494 - Sunan Abi Dawud - Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Abi Dawud)
Abu Umamat Al Bahili reported the Apostle of Allaah(ﷺ) as saying “There are three persons who are in the security of Allaah, the Exalted.” “A man who goes out on an expedition to fight in the path of Allaah, the Exalted, is in the security of Allaah, until He takes him unto Him(i.e., he dies) and brings him into Paradise or brings him(alive) with reward and booty he obtains and a man who goes to the mosque is in the security of Allaah, until he takes him unto Him(i.e., he dies), and he b
Grade: Sahih

Hadith #2501 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث; Ubda bin Sulaiman عبدة بن سليمان المروزي; Umar bin Muhammad bin al-Mnkdr عمر بن محمد بن المنكدر; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
On the day of Hunayn we travelled with the Messenger of Allah (ﷺ) and we journeyed for a long time until the evening came. I attended the prayer along with the Messenger of Allah (ﷺ). A horseman came and said: Messenger of Allah, I went before you and climbed a certain mountain where saw Hawazin all together with their women, cattle, and sheep, having gathered at Hunayn. The Messenger of Allah (ﷺ) smiled and said: That will be the booty of the Muslims tomorrow if Allah wills. He then asked
Grade: Sahih

Hadith #2510 - Sunan Abi Dawud - Abdul 'Aziz bin Marwan عبد العزيز بن مروان بن الحكم; Abdullah bin Yazid bin Zayd; Abu Hurairah; Yazid bin Zayd (Sunan Abi Dawud)
Abu Sa’id Al Khudri said “The Apostle of Allaah(ﷺ) sent an expedition towards Banu Lihyan and said “One of the two persons should go forth. He then said to those who sat (at home), If any one of you looks after the family and property of a warrior, he will receive half the reward of the one who goes forth (in jihad).”
Grade: Sahih

Hadith #2532 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Ala' bin al-Harith bin 'Abdul Warith العلاء بن الحارث بن عبد الوارث; Makhul al-Shami/al-Damashiqi مكحول الشامي; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
The Prophet (ﷺ) said: Three things are the roots of faith: to refrain from (killing) a person who utters, “There is no god but Allah” and not to declare him unbeliever whatever sin he commits, and not to excommunicate him from Islam for his any action; and jihad will be performed continuously since the day Allah sent me as a prophet until the day the last member of my community will fight with the Dajjal (Antichrist). The tyranny of any tyrant and the justice of any just (ruler) will not i
Grade: Da'if

Hadith #2536 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Our Lord Most High is pleased with a man who fights in the path of Allah, the Exalted; then his companions fled away (i.e. retreated). But he knew that it was a sin (to flee away from the battlefield), so he returned, and his blood was shed. Thereupon Allah, the Exalted, says to His angels: Look at My servant; he returned seeking what I have for him (i.e. the reward), and fearing (the punishment) I have, until his blood was shed.
Grade: Hasan

Hadith #2546 - Sunan Abi Dawud - Abu Hurairah; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to name a mare a horse.
Grade: Sahih

Hadith #2549 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
‘Abd Allaah bin Jafar said “The Apostle of Allaah(ﷺ) seated me behind him(on his ride) one day, and told me secretly a thing asking me not to tell it to anyone. The place for easing dearer to the Apostle of Allaah(ﷺ) was a mound or host of palm trees by which he could conceal himself. He entered the garden of a man from the Ansar(Helpers). All of a sudden when a Camel saw the Prophet (ﷺ) it wept tenderly producing yearning sound and it eyes flowed. The Prophet (ﷺ) came to it and wipe
Grade: Sahih

Hadith #2554 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Suhayl bin Abi Salah سهيل بن أبي صالح; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The Prophet (ﷺ) said: The angels do not go with a travelling company in which there is a bell.
Grade: Sahih

Hadith #2555 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Muhammad bin Rafa'i محمد بن رافع; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “The angels do not accompany the fellow travelers who have a dog or bell (with them).”
Grade: Sahih

Hadith #2566 - Sunan Abi Dawud - Abd al-Whab bin Njd'h عبد الوهاب بن نجدة; Abu Hurairah; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Abi 'Amr يحيى بن أبي عمرو السيباني (Sunan Abi Dawud)
‘Abd Allah bin Ja’far said “When the Prophet (ﷺ) arrived after a journey, we were taken for his reception. Any of us who met him first he lifted him in front of him. As I was the first to meet him, he lifted me in front of him. Then Hasan or Hussain was brought to him and he set him behind him. We the entered Madeenah and we (were) riding so (three on one beast).”
Grade: Sahih

Hadith #2567 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك; Muhammad bin Rafa'i محمد بن رافع; Sa'id bin Abi Hnd سعيد بن أبي هند الفزاري (Sunan Abi Dawud)
Abu Hurairah reported the Prophet(ﷺ) as saying “Do not treat the backs of your beasts as pulpits, for Allaah has made them subject to you only to convey you to a town which you cannot reach without difficulty and He has appointed the earth (a floor to work) for you, so conduct your business on it.
Grade: Sahih

Hadith #2568 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “There are Camels which belong to devils and there are houses which belong to devils. As for the Camels of the devils, I have seen them. One of you goes out with his side Camels which he has fattened neither riding any of them nor giving a lift to a tired brother when he meets. As regard the houses of the devils, I have not seen them. The narrator Sa’id says “I think they are those cages (Camel litters) which conceal people with br
Grade: Da'if

Hadith #2573 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Nafi' bin Abi Nafi' نافع بن أبي نافع البزاز (Sunan Abi Dawud)
My foster-father said to me – he was one of Banu Murrah ibn Awf, and he was present in that battle, the battle of Mu’tah: By Allah, as if I am seeing Ja’far who jumped from his reddish horse and hamstrung it; he then fought with the people until he was killed. Abu Dawud said: The tradition is not strong.
Grade: Hasan

Hadith #2578 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ali bin Muslim bin Sa'id علي بن مسلم بن سعيد الطوسي; Husayn bin Nmyr al-Kndy Thm حصين بن نمير; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Hussain bin al-Hasan سفيان بن حسين السلمي (Sunan Abi Dawud)
while she was on a journey along with the Messenger of Allah (ﷺ): I had a race with him (the Prophet) and I outstripped him on my feet. When I became fleshy, (again) I had a race with him (the Prophet) and he outstripped me. He said: This is for that outstripping.
Grade: Sahih

Hadith #2597 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
Al-Muhallab ibn AbuSufrah said: A man who heard the Prophet (ﷺ) say: If the enemy attacks you at night, let your war cry be Ha-Mim. They will not be helped.
Grade: Sahih

Hadith #2608 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Bhr bin Bry علي بن بحر بن بري; Hatm bin Isma'il al-Madni حاتم بن إسماعيل المدني; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Nafie' نافع مولى ابن عمر (Sunan Abi Dawud)
The Prophet (ﷺ) said: When three are on a journey, they should appoint one of them as their commander.
Grade: Hasan Sahih

Hadith #2639 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to keep to the rear when travelling and urge on the weak. He would take someone up behind him and make supplication for them all.
Grade: Sahih

Hadith #2659 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: There is jealousy which Allah loves and jealousy which Allah hates. That which Allah loves is jealousy regarding a matter of doubt, and that which Allah hates is jealousy regarding something which is not doubtful. There is pride which Allah hates and pride which Allah loves. That which Allah loves is a man’s pride when fighting and when giving sadaqah and that which Allah hates is pride shown by oppression. The narrator Musa said: “by boasting.”
Grade: Hasan

Hadith #2673 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Bukayr bin 'Abdullah bin al-Ashj بكير بن عبد الله بن الأشج; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Yazid bin Khalid bin Yazid يزيد بن خالد بن يزيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) appointed him commander over a detachment. He said: I went out along with it. He (the Prophet) said: If you find so-and-so, burn him with the fire. I then turned away, and he called me. So I returned to him, and he said: If you find so-and-so, kill him, and do not burn him, for no one punishes with fire except the Lord of the fire.
Grade: Sahih

Hadith #2676 - Sunan Abi Dawud - Abu Hurairah; Hammad bin Salama حماد بن سلمة; Muhammad bin Ziyad محمد بن زياد القرشي; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) announced to go on expedition for Tabuk. I went to my family and then proceeded (on journey). The vanguard of the Companions of the Messenger of Allah (ﷺ) had already proceeded. So I began to announce loudly in Medina: Is there anyone who takes a man on his ride, and he will get his share (from the booty? An old man from the Ansar (Helpers) spoke loudly: We shall have his share if we take him with us on our mount by turns, and he will have his meal with us. I said:
Grade: Hasan

Hadith #2678 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent Abdullah ibn Ghalib al-Laythi along with a detachment and I was also with them. He ordered them to attach Banu al-Mulawwih from all sides at al-Kadid. So we went out and when we reached al-Kadid we met al-Harith ibn al-Barsa al-Laythi, and seized him. He said: I came with the intention of embracing Islam, and I came out to go to the Messenger of Allah (ﷺ). We said: If you are a Muslim, there is no harm if we keep you in chains for a day and night; and if you
Grade: Da'if

Hadith #2710 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
A man from the Companions of the Prophet (ﷺ) died on the day of Khaybar. They mentioned the matter to the Messenger of Allah. He said: Offer prayer over your companion. When the faces of the people looked perplexed, he said: Your companion misappropriated booty in the path of Allah. We searched his belongings and found some Jewish beads not worth two dirhams.
Grade: Hasan

Hadith #2722 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Sa'id bin al-'As bin Sa'id bin al-'As; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Unbasa bin Sa'id bin al-Durays عنبسة بن سعيد بن الضريس (Sunan Abi Dawud)
At the battle of Badr the Messenger of Allah gave me AbuJahl’s sword, as I had killed him.
Grade: Da'if

Hadith #2723 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hamd bin Yahya bin Han'i حامد بن يحيى بن هانئ; Sufyan bin 'Uyaynah سفيان بن عيينة; Unbasa bin Sa'id bin al-Durays عنبسة بن سعيد بن الضريس (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent AbuSa’id ibn al-‘As with an expedition from Medina towards Najd. Aban ibn Sa’id and his companions came to the Messenger of Allah (ﷺ) at Khaybar after it had been captured. The girths of their horses were made of palm fibres. Aban said: Give us a share (from the booty), Messenger of Allah. AbuHurayrah said: I said: Do not give them a share, Messenger of Allah. Aban said: Why are you talking so, Wabr. You have come to us from the peak of Dal. The Prophet
Grade: Sahih

Hadith #2756 - Sunan Abi Dawud - Abdur Rahman bin Abi al-Zanad عبد الرحمن بن أبي الزناد; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Abi Dawud)
Ibn ‘Umar reported the Apostle of Allaah(ﷺ) as saying “A banner will be hoisted for a treacherous man on the Day of Judgment, it will then be announced. This is a treachery of so and so, son of so and so.
Grade: Sahih

Hadith #2768 - Sunan Abi Dawud - Abdur Rahman bin Abi Karima عبد الرحمن بن أبي كريمة; Abu Hurairah; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Isma'il bin 'Abdur Rahman al-Saddi إسماعيل بن عبد الرحمن السدي (Sunan Abi Dawud)
The Messenger of Allah ( may peace be upon him) said : Who will pursue Ka’b bin Al-Ashraf, for he has caused trouble to Allah and His Apostle? Muhammad bin Maslamah stood up and said: I (shall do), Messenger of Allah. Do you want that I should kill him? He said: Yes. He said: So permit me to say something (against you). He said: Yes say. He then came to him (Ka’b b. al-Ashraf) and said to him: This man has asked us for sadaqah (alms) and has put us into trouble. He (Ka’b) said: You will be
Grade: Sahih

Hadith #2830 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id bin Abi Sa'id; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
A man called the Messenger of Allah (ﷺ): We used to sacrifice Atirah in pre-Islamic days during Rajab; so what do you command us? He said: Sacrifice for the sake of Allah in any month whatever; obey Allah, Most High, and feed(the people). He said: We used to sacrifice a Fara’ in pre-Islamic days, so what do you command us? He said: On every pasturing animal there is a Fara’ which is fed by your cattle till it becomes strong and capable of carrying load. The narrator Nasr said (in his versi
Grade: Sahih

Hadith #2843 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
When a boy was born to one of us in the pre-Islamic period, we sacrificed a sheep and smeared his head with its blood; but when Allah brought Islam, we sacrificed a sheep, shaved his head and smeared his head with saffron.
Grade: Hasan Sahih

Hadith #2859 - Sunan Abi Dawud - Abu Hurairah; Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي; al-Hasan bin al-Hakam al-Nkh'y الحسن بن الحكم النخعي; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي (Sunan Abi Dawud)
The Prophet (ﷺ) said: (the narrator Sufyan said: I do not know but that it has been transmitted from the Prophet (ﷺ): He who lives in the desert will become rude; he who pursues the game will be negligent, and he who visits a king will be perverted.
Grade: Sahih

Hadith #2864 - Sunan Abi Dawud - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Abu Hurairah; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
On the authority of his father (Sa’d b. Abi Waqqas): When he (Sa’d) fell ill at Mecca (according to the version of Ibn Abi Kkalaf) – then the agreed version has: which brought him near to death – the Messenger of Allah (ﷺ) went to visit him. He said: Messenger of Allah, I have a large amount of property, and my daughter is my only heir. May I give two-thirds (of my property) as a sadaqah (charity)? He said: No. He asked: Then a half ? He replied: No. He asked: Then one-third ? He repli
Grade: Sahih

Hadith #2866 - Sunan Abi Dawud - Abdah bin 'Abdullah al-Saffar عبدة بن عبد الله الصفار; Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Abu Hurairah; Nasr bin 'Ali bin Nasr bin 'Ali; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man giving a dirham as sadaqah (charity) during his life is better than giving one hundred dirhams as sadaqah (charity) at the moment of his death.
Grade: Da'if

Hadith #2873 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Salm Abu al-Ghyth al-Madni سالم أبو الغيث المدني مولى; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Thur bin Zayd al-Dayli ثور بن زيد (Sunan Abi Dawud)
I memorised (a tradition) from the Messenger of Allah (ﷺ): There is no orphanhood after puberty, and there is no silence for the whole day till the night.
Grade: Sahih

Hadith #2879 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; al-Rabi' bin Sulaiman الربيع بن سليمان; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
‘Abd al-Hamid b. Abd ‘Allah b. ‘Abd Allah b. ‘Umar b. al-Khattab copied to me a document about the religious endowment (waqf) made by ‘Umar b. al-Khattab : In the name of Allah, the Compassionate, the Merciful. This is what Allah’s servant ‘Umar has written about Thamgh. He narrated the tradition like the one transmitted by Nafi’. He added: “provided he is not storing up goods (for himself)”. The surplus fruit will be devoted to the beggar and the deprived. He then went on wi
Grade: Sahih

Hadith #2919 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abu Hurairah; Ibn Ishaq محمد بن إسحاق بن يسار‎; Yazid bin 'Abdullah bin Qasayt يزيد بن عبد الله بن قسيط (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade selling or giving away the right to inheritance by a manumitted slave.
Grade: Sahih

Hadith #2954 - Sunan Abi Dawud - Abu Hurairah; Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Prophet (ﷺ) said: I am nearer to the believers than themselves, so if anyone leaves property, it goes to his heirs, and if anyone leaves debt and dependants, let the matter come to me and I shall be responsible.
Grade: Sahih

Hadith #2973 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
AbutTufayl said: Fatimah came to AbuBakr asking him for the inheritance of the Prophet (ﷺ). AbuBakr said: I heard the Messenger of Allah (ﷺ) say: If Allah, Most High, gives a Prophet some means of sustenance, that goes to his successor.
Grade: Hasan

Hadith #3002 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: If you gain a victory over the men of Jews, kill them. So Muhayyisah jumped over Shubaybah, a man of the Jewish merchants. He had close relations with them. He then killed him. At that time Huwayyisah (brother of Muhayyisah) had not embraced Islam. He was older than Muhayyisah. When he killed him, Huwayyisah beat him and said: O enemy of Allah, I swear by Allah, you have a good deal of fat in your belly from his property.
Grade: Da'if

Hadith #3023 - Sunan Abi Dawud - Abdullah bin Rbah عبد الله بن رباح الأنصاري أبو خالد; Abu Hurairah; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Salam bin Mskyn bin Rabi'ya سلام بن مسكين بن ربيعة; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Wahb bin Munabbih said “I sked Jabir “Did they get any booty on the day of conquest (of Makkah)? He replied, No.
Grade: Sahih

Hadith #3034 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Suhayl bin Abi Salah سهيل بن أبي صالح; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Malik said “’Umar expelled the Jews of Najran and Fadak.”
Grade: Sahih

Hadith #3084 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) protected Naqi and said: There is no (permission for) protected land except for Allah Most High.
Grade: Sahih

Hadith #3111 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came to visit Abdullah ibn Thabit who was ill. He found that he was dominated (by the divine decree). The Messenger of Allah (ﷺ) called him loudly, but he did not respond. He uttered the Qur’anic verse “We belong to Allah and to Him do we return” and he said: We have been dominated against you, AburRabi’. Then the women cried and wept, and Ibn Atik began to silence them. The Messenger of Allah (ﷺ) said: Leave them, when the divine decree is made, no woman
Grade: Sahih

Hadith #3160 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Qasim bin 'Abbas bin Muhammad القاسم بن عباس بن محمد; Amr bin 'Umayr عمرو بن عمير; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Abi Fadayk محمد بن إسماعيل بن مسلم بن أبي فديك (Sunan Abi Dawud)
The Prophet (ﷺ) used to take a bath on account of sexual defilement, on Friday, for cupping and washing the dead.
Grade: Hasan

Hadith #3161 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Ishaq Mwla Za'id'h إسحاق مولى زائدة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who washes the dead should take a bath, and he who carries him should perform ablution.
Grade: Sahih

Hadith #3170 - Sunan Abi Dawud - Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Harb bin Shadaad al-Yashkari حرب بن شداد اليشكري; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
I heard the Prophet (ﷺ) say: If any Muslim dies and forty men associate nothing with Allah stand over his bier. Allah will accept them as intercessors for him.
Grade: Sahih

Hadith #3190 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Salah bin Nubhan صالح بن نبهان; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I swear by Allah, the Messenger of Allah (ﷺ) prayed in the mosque over the two sons of al-Baida’: Suhail and his brother.
Grade: Sahih

Hadith #3198 - Sunan Abi Dawud - Abdul 'Aziz bin Yahya bin Yusuf عبد العزيز بن يحيى بن يوسف البكائي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي (Sunan Abi Dawud)
I prayed over a dead person along with Ibn ‘Abbas. He recited Surat al-Fatihah and he said: This is the Sunnah.
Grade: Sahih

Hadith #3200 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Musa bin Mrwan موسى بن مروان; Shu'aib bin Ishaq bin 'Abdur Rahman شعيب بن إسحاق بن عبد الرحمن; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
I was present with Marwan who asked AbuHurayrah: Did you hear how the Messenger of Allah (ﷺ) used to pray over the dead? He said: Even with the words that you said. (The narrator said: They exchanged hot words between them before that.) Abu Hurairah said: O Allah, Thou art its Lord. Thou didst create it, Thou didst guide it to Islam, Thou hast taken its spirit, and Thou knowest best its inner nature and outer aspect. We have come as intercessors, so forgive him. Abu Dawud said: Shu’bah made
Grade: Hasan

Hadith #3202 - Sunan Abi Dawud - Abu Hurairah; Abu Rafi'; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Harb سليمان بن حرب; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) led us in prayer over bier of a Muslim and I heard him say: O Allah, so and so, son of so and so, is in Thy protection, so guard him from the trial in the grave. (AbdurRahman in his version said: “In Thy protection and in Thy nearer presence, so guard him from the trial in the grave) and the punishment in Hell. Thou art faithful and worthy of praise. O Allah, forgive him and show him mercy. Thou art the forgiving and the merciful one.” AbdurRahman said: “On the
Grade: Sahih

Hadith #3203 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
A negress (or a youth) used to sweep the mosque. The Prophet (ﷺ) missed him, and when he asked about him the people told him that he had died. He said: Why have you not informed me ? He said: Lead me to his grave. So they led him and he prayed over him.
Grade: Sahih

Hadith #3226 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
‘Uthman said: “or anything added to it.” Sulaiman b. Musa said: “or anything written on it.” Musaddad did not mention in his version the words “or anything added to it.” Abu Dawud said: The word “and that” (wa an) remained hidden to me.
Grade: Sahih

Hadith #3227 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Allah’s curse to be on the Jews, they made the graves of their Prophets mosques.
Grade: Sahih

Hadith #3232 - Sunan Abi Dawud - Abu Hurairah; Amir bin Sa'd ibn Abi Waqqas عامر بن سعد بن أبي وقاص; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
A man was buried with my father. I had a desire at heart for that (place for my burial). So I took him out after six months. I did not find any change (in his body) except a few hair that touched the earth.
Grade: Sahih

Hadith #3233 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Abu Hurairah; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Yazid bin Kysan al-Yshkry يزيد بن كيسان اليشكري أبو إسماعيل (Sunan Abi Dawud)
People with a bier passed by the Messenger of Allah (ﷺ). They (the companions) spoke highly of him. He said: Paradise is certain for him. Then some people with another (bier) passed by him. They spoke very badly of him. He said: Hell is certain for him. He then said: Some of you are witness to others.
Grade: Sahih

Hadith #3236 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) cursed women who visit graves, those who built mosques over them and erected lamps (there).
Grade: Da'if

Hadith #3246 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) said: One should not take a false oath at this pulpit of mine even on a green tooth-stick; otherwise he will make his abode in Hell, or Hell will be certain for him.
Grade: Sahih

Hadith #3247 - Sunan Abi Dawud - Abu Hurairah; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Ibn Sirin محمد بن سيرين الأنصاري; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone swears on oath is the course which he says: “By al-Lat” he should say: There is no god but Allah, and that if anyone says to his friend: Come and let me play for money with you, he should give something in charity (sadaqah).
Grade: Sahih

Hadith #3254 - Sunan Abi Dawud - Abu Hurairah; Amr bin 'Awn/'Auf bin Aws; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said about the futile oath: It is man’s speech in his house: No, by Allah, and Yes, by Allah. Abu Dawud said: Ibrahim al-Sa’igh, the narrator of this tradition , was a pious man. Abu Muslim killed him at ‘Aranda. When he raised a hammed and heard the call to prayer, he gave it up. Abu Dawud said: This tradition has been transmitted by Dawud b. Abi al-Furat from Ibrahim al-Sa’igh as a statement of ‘Aishah (not attributed to the Prophet). Similarly, it has be
Grade: Sahih

Hadith #3264 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin 'Abdul 'Aziz bin Abi Razma محمد بن عبد العزيز بن أبي رزمة; Muhammad bin Hilal bin Aby محمد بن هلال بن أبي هلال المدني; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) swore an oath strongly, he said: No, by Him in Whose hand is the soul of AbulQasim.
Grade: Da'if

Hadith #3267 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
AbuBakr adjured the Prophet (ﷺ). The Prophet (ﷺ) said: Do not adjure an oath.
Grade: Sahih

Hadith #3287 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade to make a vow. He said: It has not effect against fate, it is only from the miserly that it is means by which something is extracted. Musaddad said: The Messenger of Allah (ﷺ) said: A vow does not avert anything (i.e. has no effect against fate).
Grade: Sahih

Hadith #3330 - Sunan Abi Dawud - Aabad bin Rashid al-Tamimi عباد بن راشد التميمي مولاهم البصري البزا; Abu Hurairah; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sa'id bin Abi Khyrh سعيد بن أبي خيرة (Sunan Abi Dawud)
I heard Messenger of Allah (ﷺ) say: But between them are certain doubtful things which many people do not recognize. He who guards against doubtful things keeps his religion and his honor blameless, but he who falls into doubtful things falls into what is unlawful.
Grade: Sahih

Hadith #3334 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Unbasa bin Sa'id bin al-Aas عنبسة بن سعيد بن العاص بن سعيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
On the authority of his father: I heard the Messenger of Allah (ﷺ) say in the Farewell Pilgrimage: “Lo, all claims to usury of the pre-Islamic period have been abolished. You shall have your capital sums, deal not unjustly and you shall not be dealt with unjustly. Lo, all claims for blood-vengeance belonging to the pre-Islamic period have been abolished. The first of those murdered among us whose blood-vengeance I remit is al-Harith ibn AbdulMuttalib, who suckled among Banu Layth and killed
Grade: Sahih

Hadith #3344 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
“He (the Prophet) purchased a calf from a caravan, but he had no money with him. He then sold it with some profit and gave the profit in charity to the poor and widows of Banu ‘Abd al-Muttalib. He then said: I shall not buy anything after this but only when I have money with me.
Grade: Da'if

Hadith #3363 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Da'ud bin al-Husain al-Amwy داود بن الحصين الأموي; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade the sale of fruits for dried dates, but gave license regarding the ‘araya for its sale on the basis of a calculation of their amount. But those who buy them can eat them when fresh.
Grade: Sahih

Hadith #3368 - Sunan Abi Dawud - Abu Hurairah; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Khumayr al-Rahbi يزيد بن خمير (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade selling palm-trees till the dates began to ripen, and ears of corn till they were white and were safe from blight, forbidding it both to the buyer and to the seller.
Grade: Sahih

Hadith #3375 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Abi Dawud)
The Prophet (ﷺ) forbade sale of fruits for a number of years. One of the two narrators (Abu al-Zubair and Sa’id b. Mina’) mentioned the words “sale for years” (bai’ al-sinin instead of al-mu’awamah).
Grade: Sahih

Hadith #3424 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Abu Hurairah; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin Jahada محمد بن جحادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
That Abu Tibah cupped the Messenger of Allah (ﷺ) and he ordered that a sa’ of dates be given to him, also ordering his people to remit some of his dues.
Grade: Sahih

Hadith #3436 - Sunan Abi Dawud - Abu Hurairah; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Ubaidullah bin 'Amr bin Abi Walid عبيد الله بن عمرو بن أبي الوليد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: None of you must buy in opposition to one another ; and do not go out to meet the merchandise, (but one must wait) till it is brought down to the market.
Grade: Sahih

Hadith #3437 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Do not go our to meet what is being brought (to market for sale). If anyone does so and buys some of it, the owner of merchandise has a choice (of canceling the deal) when it comes to the market. Abu ‘Ali said: I heard Abu Dawud say: Sufyan said: none of you must buy in opposition to one another ; that is he says: I have a better one for ten (dirhams).
Grade: Sahih

Hadith #3442 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: A townsman must not sell for a man from the desert ; and leave people alone, Allah will give them provision from one another.
Grade: Sahih

Hadith #3443 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Do not go out to meet riders to conduct business with them ; none of you must buy in opposition to one another; and do not tie up the udders of camels and sheep, for he who buys them after that has been done has two courses open to him after milking them: he may keep them if he is pleased with them, or he may return them along with a sa’ of dates is he is displeased with them.
Grade: Sahih

Hadith #3444 - Sunan Abi Dawud - Abdullah bin Mkhld عبد الله بن مخلد; Abu Hurairah; Ibn Jurayj ابن جريج; Makki bin Ibrahim bin Bashayr مكي بن إبراهيم بن بشير; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: If anyone buys sheep whose udders have been tied up, he has option for three days: he may return it if he desires with a sa’ of any grain, not (necessarily) wheat.
Grade: Sahih

Hadith #3449 - Sunan Abi Dawud - Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Muhammad bin 'Uthman al-Tnwkhy محمد بن عثمان التنوخي أبو الجماهر; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
On the authority of his father, who said: The Messenger of Allah (ﷺ) forbade to break the coins of the Muslims current among them except for some defect.
Grade: Da'if

Hadith #3451 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The people said: Messenger of Allah , prices have shot up, so fix prices for us. Thereupon the Messenger of Allah (ﷺ) said: Allah is the one Who fixes prices, Who withholds, gives lavishly and provides, and I hope that when I meet Allah, none of you will have any claim on me for an injustice regarding blood or property.
Grade: Sahih

Hadith #3457 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Hatm bin Yonus محمد بن حاتم بن يونس; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
We fought one of our battle, and encamped at a certain place. One of our companions sold a horse for a slave. After that they remained there for the rest of day and night. When the next morning came, they prepared themselves for departure. The buyer of the horse began to saddle it, but the seller was ashamed (of the transaction). He went to the man (buyer) and asked him to annul the transaction. The man refused to hand it over (the horse) to him. He said: AbuBarzah, the companion of the Prophet
Grade: Sahih

Hadith #3459 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hafs bin Ghyath حفص بن غياث; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Yahya bin Ma'in يحيى بن معين (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Both parties in a business transaction have a right of option (to annul it) so long as they are not separated ; and if they tell the truth and make everything clear, they will be blessed in their transaction, but it they conceal anything and lie, the blessing on their transaction will be blotted out. Abu Dawud said: A similar tradition has also been transmitted by Sa’id b. Abi ‘Arubah and Hammad. As regards with Hammam, he said in his version: Until th
Grade: Sahih

Hadith #3460 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone rescinds a sale with a Muslim, Allah will cancel his slip, on the Day of Resurrection.
Grade: Sahih

Hadith #3472 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
Blight is not effective when less than one-third of goods are damaged. Yayha said: That has been the established practice of Muslims.
Grade: Hasan

Hadith #3473 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: Excess water should not be withheld so as to prevent (cattle) by it from grass.
Grade: Sahih

Hadith #3483 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Ma'rwf bin Suwayd al-Jdhamy معروف بن سويد الجذامي أبو سلمة المصري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ)forbade the price paid for a dog.
Grade: Sahih

Hadith #3484 - Sunan Abi Dawud - Abd al-Whab bin Bkht عبد الوهاب بن بخت; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
The Prophet (ﷺ) said: The price paid for a dog, the price given to a soothsayer, and the hire paid to a prostitute are not lawful.
Grade: Sahih

Hadith #3514 - Sunan Abi Dawud - Abdullah bin Idris bin Yazid al-Audi عبد الله بن إدريس بن يزيد الأودي; Abu Hurairah; al-Hasan bin al-Rabi' al-Bajli الحسن بن الربيع; Ibn Jurayj ابن جريج; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) decreed the right to buy the neighboring property applicable to everything which is not divided, but when boundaries are fixed and separate roads made, there is no option.
Grade: Sahih

Hadith #3518 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Bakr bin Muhammad bin 'Amr bin Hazm أبو بكر بن محمد بن عمرو بن حزم; Abu Hurairah; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Umar bin ‘Abdul-‘Aziz عمر بن عبد العزيز; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) said: The neighbour is most entitled to the right of pre-emption, and he should wait for its exercise even if he is absent, when the two properties have one road.
Grade: Sahih

Hadith #3521 - Sunan Abi Dawud - Abdullah bin 'Abdur Jabbar عبد الله بن عبد الجبار الخبائري زبريق; Abu Bakr bin 'Abdur Rahman أبو بكر بن عبد الرحمن بن الحارث بن هشام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي (Sunan Abi Dawud)
“If he paid something from the price (of the property), then he will be equal to the creditors in it.”
Grade: Sahih

Hadith #3525 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Hurairah; Amir al-Sha'bi عامر الشعبي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone leaves an animal at a place of perishing and another man brings it to life, it belongs to him who brings it to life.
Grade: Hasan

Hadith #3534 - Sunan Abi Dawud - Abu Hurairah; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Talq bin Ghanam طلق بن غنام; Uthman bin 'Asim bin Husayn عثمان بن عاصم بن حصين أبو حصين (Sunan Abi Dawud)
I used to write (the account of) the expenditure incurred on orphans who were under the guardianship of so-and-so. They cheated him by one thousand dirhams and he paid these (this amount) to them. I then got double the property which they deserved. I said (to the man: Take one thousand (dirhams) which they have taken from you (by cheating). He said: No, my father has told me that he heard the Messenger of Allah (ﷺ) say: Pay the deposit to him who deposited it with you, and do not betray him wh
Grade: Sahih

Hadith #3536 - Sunan Abi Dawud - Abu Hurairah; Ibn Ishaq محمد بن إسحاق بن يسار‎; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Sa'id bin Abi Sa'id; Salmah bin al-Fadl al-Abrash سلمة بن الفضل الأبرش (Sunan Abi Dawud)
That the Prophet (ﷺ) used to accept a gift and make return for it.
Grade: Sahih

Hadith #3547 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is not permissible for a woman to present a gift (from her husband’s property) except with the permission of her husband.
Grade: Hasan Sahih

Hadith #3570 - Sunan Abi Dawud - Abu Hurairah; Amr bin Abi 'Amr; Fdyl bin Sulaiman al-Nmyry فضيل بن سليمان النميري; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
Al-Bara’ had a she-camel which was accustomed to graze the standing crop belonging to the people. She entered a garden and did damage to it. The Messenger of Allah (ﷺ) was informed about it. So he gave decision that the owners of gardens are responsible for guarding them by day, and the owners of the animals are responsible for guarding them by night. Any damage done by animals during the night is a responsibility lying on their owners.
Grade: Sahih

Hadith #3571 - Sunan Abi Dawud - Abdullah ibn Ja'far; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; Nasr bin 'Ali bin Nasr bin 'Ali; Sa'id bin Abi Sa'id; Uthman bin Muhammad bin al-Mughira عثمان بن محمد بن المغيرة بن الأخنس (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who has been appointed a judge has been killed without a knife.
Grade: Sahih

Hadith #3574 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abu Hurairah; Malazm bin 'Amr - Lazaym ملازم بن عمرو اليمامي - لزيم; Musa bin Njd'h al-Hnfy موسى بن نجدة الحنفي اليمامي; Umar bin Yonus bin al-Qasim عمر بن يونس بن القاسم (Sunan Abi Dawud)
‘If a judge passes a judgment having exerted himself to arrive at what is correct, and he is indeed correct, he will have two rewards. If he passes judgment having exerted himself to arrive at what is correct, but it is incorrect, he will have one reward.'” I narrated it to Abu Bakr bin Hazm and he said: “This is what Abu Salamah narrated to me from Abu Hurairah.
Grade: Sahih

Hadith #3593 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Kathir bin Zayd al-'Aslmy كثير بن زيد الأسلمي; Mrwan bin Muhammad bin Hsan مروان بن محمد بن حسان الأسدي; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
Mu’adh bin Jabal said that when the Messenger of Allah (ﷺ) sent him to the Yemen… He then narrated the rest of the tradition to the same effect.
Grade: Da'if

Hadith #3601 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: The testimony of a deceitful man or woman, of an adulterer and adulteress, and of one who harbours rancour against his brother is not allowable.
Grade: Hasan

Hadith #3609 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Rabi'ya bin Abi 'Abdur Rahman; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
‘Amr said: In the rights (of the people).
Grade: Sahih

Hadith #3615 - Sunan Abi Dawud - Abu Hurairah; Abu Rafi'; Khalas bin 'Amr al-Hajri خلاس بن عمرو الهجري; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Qatadah through a different chain of narrators to the effect that two men laid claim camel and both of them produced witness so the prophet (peace be upon him) divided it in halves between them.
Grade: Hasan

Hadith #3616 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد; Salmah bin Shbyb سلمة بن شبيب (Sunan Abi Dawud)
Two men disputed about some property and brought the case to the Holy Prophet (ﷺ), but neither of them could produce any proof. So the Holy Prophet (ﷺ) said: Cast lots about the oath whatever it may be, whether they like it or dislike it.
Grade: Sahih

Hadith #3623 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Abi Dawud)
A man from Hadramaw and a man from kindah came to the Messenger of Allah (ﷺ). The hadrami said: Messenger of Allah, this (man) has seized land which belonged to my father. Al-Kindi said: That is my land in my possession and I cultivate it; he has no right to it. The Holy prophet (may be peace upon him) said to the Hadrami: Have you any proof? We said : No. he (the Prophet)said: Then he will swear an oath for you . He said: Messenger of Allah, he is a reprobate and he would not care to swear t
Grade: Sahih

Hadith #3632 - Sunan Abi Dawud - Abu Hurairah; Bashyr bin Ka'b bin Aby بشير بن كعب بن أبي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
I intended to go (on expedition) to Khaybar. So I came to the Holy Prophet (ﷺ), greeted him and said: I am intending to go to Khaybar. He said: When you come to my agent, you should take from him fifteen wasqs (of dates). If he asks you for a sign, then place your hand on his collar-bone.
Grade: Da'if

Hadith #3633 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If you dispute over a pathway, leave the margin of seven yards.
Grade: Sahih

Hadith #3642 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Abu al-Darda through a different chain of narrators to the same effect from the Holy Prophet (ﷺ)
Grade: Sahih

Hadith #3648 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
When Mecca was conquered, the Holy Prophet (peace be upon him) stood up. He (Abu Hurairah) then mentioned the sermon of the Holy Prophet (ﷺ). He said: A man of the Yemen, who was called Abu Shah, got up and said: Messenger of Allah! Write it for me. He said: Write it for Abu Shah.
Grade: Sahih

Hadith #3656 - Sunan Abi Dawud - Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Bakr bin 'Amr al-Ma'fari بكر بن عمرو المعافري; Muslim bin Yasar al-'Abbassri مسلم بن يسار البصري - مسلم سكرة المصبح; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي (Sunan Abi Dawud)
The Holy Prophet (ﷺ) forbade the discussion of thorny questions.
Grade: Da'if

Hadith #3657 - Sunan Abi Dawud - Abu Hurairah; Ata' bin Abi Rabah عطاء بن أبي رباح; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone is given a legal decision ignorantly, the sin rests on the one who gave it. Sulayman al-Mahri added in his version: If anyone advises his brother, knowing that guidance lies in another direction, he has deceived him. These are the wordings of Sulayman.
Grade: Hasan

Hadith #3661 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ali bin Ms'hr علي بن مسهر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
I swear on Allah, it will be better for you that Allah should give guidance to one man through your agency than that you should acquire the red ones among the camels.
Grade: Sahih

Hadith #3663 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Falayh bin Suliaman فليح بن سليمان; Sa'id bin Yasar, Abu al-Hubab سعيد بن يسار أبو الحباب; Surayj bin al-Nu'man al-Juhari سريج بن النعمان الجوهري اللؤلؤي (Sunan Abi Dawud)
The Prophet (ﷺ) used to relate to us traditions from the children of Isra’il till morning came; he would not get up except for obligatory prayer.
Grade: Da'if

Hadith #3677 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Hurairah; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Wine is made from grape-syrup, raisins, dried dates, wheat, barley, millet, and I forbid you from every intoxicant.
Grade: Sahih

Hadith #3692 - Sunan Abi Dawud - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Abu Hurairah; Ibn Sirin محمد بن سيرين الأنصاري; Nwh bin Qays bin نوح بن قيس بن; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The deputation of ‘Abd al-Qais came to Messenger of Allah (ﷺ) and said: This is the tribe of Rabi’ah, and the infidels of Mudar are between us and you. We are able to come to you only in the sacred month. So give a decisive command which we may follow ourselves and to which we call those at home behind us. He (the Prophet) said: I command you to observe four things, and forbade you four things: Belief in Allah. the testimony that there is no god but Allah, and he expresses one by folding h
Grade: Sahih

Hadith #3715 - Sunan Abi Dawud - Abu Hurairah; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Khalid bin 'Abdullah خالد بن عبد الله بن حسين; Sdqh bin Khalid al-Amwy صدقة بن خالد الأموي; Zayd bin Waqd al-Quraishi زيد بن واقد القرشي (Sunan Abi Dawud)
The Messenger of Allah(ﷺ) liked sweet meats and honey. The narrator then mentioned a part of the tradition mentioned above. The Messenger of Allah (ﷺ) felt it hard on him to find smell from him. In this tradition saudah said: but you ate gum ? He said : No, I drank honey. Hafsah gave it to me to drank. I said : Its bees ate ‘urfut. Abu Dawud said: Maghafir is a gum ; jarasat means ate; ’urfut is a bees ‘ plant.
Grade: Sahih

Hadith #3741 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who does not accept an invitation which he receives has disobeyed Allah and His Apostle, and he who enters without invitation enters as a thief and goes out as a raider. Abu Dawud said: Aban bin Tariq is unknown.
Grade: Da'if

Hadith #3748 - Sunan Abi Dawud - Abu Hurairah; Asim al-Ahwal عاصم الأحول; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin Mhbwb al-Binany محمد بن محبوب البناني; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
He who believes in Allah and the Last Day should honour his guest provisions for the road are what will serve for a day and night: hospitality extends for three days; what goes after that is sadaqah(charity): and it is not allowable that a guest should stay till he makes himself an encumbrance. Abu Dawud said: Malik was asked about the saying of the Prophet: “Provisions for the road what will serve for a day a night.” He said: He should honor him, present him some gift, and protect him for a
Grade: Sahih

Hadith #3762 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came out from the valley of a mountain where he had eased himself. There were some dried dates on a shield before us. We called him and he ate with us. He did not touch water.
Grade: Da'if

Hadith #3798 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Abu Thaur al-Kalbi إبراهيم بن خالد أبو ثور الكلبي; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة (Sunan Abi Dawud)
I accompanied the Messenger of Allah (ﷺ), but I did not hear about the prohibition of (eating) insects and little creatures of land.
Grade: Da'if

Hadith #3841 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hassan ibn Ali bin Abi Talib; Ma'mar bin Rashid معمر بن راشد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
A mouse fell into clarified butter. The Prophet (ﷺ) was informed of it. He said: Throw what is around it and eat.
Grade: Sahih

Hadith #3843 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The tradition mentioned above (No. 3833) has also been transmitted by Ibn Abbas from Maymunah, from the Prophet (ﷺ) like the tradition narrated by az-Zuhri, from Ibn al-Musayyab.
Grade: Da'if

Hadith #3845 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Da'ud bin Qays al-Fra'a داود بن قيس الفراء الدباغ; Musa bin Yasar al-Urdani موسى بن يسار الأردني (Sunan Abi Dawud)
If the morsel of one of you falls down, he should wipe away anything injurious on it and eat it and not leave it for the devil. And he ordered us to clean the dish, for one of you does not leave it for the devil. And he ordered us to clean the dish, for one of you does not know in what part of his food the blessing lies.
Grade: Sahih

Hadith #3851 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Suhayl bin Abi Salah سهيل بن أبي صالح; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) ate or drank, he said: “Praise be to Allah Who has given food and drink and made it easy to swallow, and provided an exit for it.
Grade: Sahih

Hadith #3856 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) came to visit me, accompanied by Ali who was convalescing. We had some ripe dates hung up. The Messenger of Allah (ﷺ) got up and began to eat from them. Ali also got up to eat, but the Messenger of Allah (ﷺ) said repeatedly to Ali: Stop, Ali, for you are convalescing, and Ali stopped. She said: I then prepared some barley and beer-root and brought it. The Messenger of Allah (ﷺ) then said: Take some of this, Ali, for it will be more beneficial for you. AbuDawud
Grade: Hasan

Hadith #3860 - Sunan Abi Dawud - Abu Hurairah; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Sa'id bin 'Abdur Rahman bin 'Abdullah سعيد بن عبد الرحمن بن عبد الله بن حميل (Sunan Abi Dawud)
The Prophet (ﷺ) had himself cupped three times in the veins at the sides of the neck and on the shoulder. Ma’mar said: I got myself cupped, and I lost my memory so much so that I was instructed Surat al-Fatihah by others in my prayer. He had himself cupped at the top of his head.
Grade: Sahih

Hadith #3869 - Sunan Abi Dawud - Abu Hurairah; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Mujahid bin Jabir مجاهد بن جبر; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: If I drink an antidote, or tie an amulet, or compose poetry, I am the type who does not care what he does. Abu Dawud said: THis was peculiar to the Prophet (ﷺ), but some people have allowed to use it, i.e. antidote.
Grade: Da'if

Hadith #3871 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
When a physician consulted the Prophet (ﷺ) about putting frogs in medicine, he forbade him to kill them.
Grade: Sahih

Hadith #3878 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Wear your white garments, for they are among your best garments, and shroud your dead in them. Among the best types of collyrium you use is antimony (ithmid): it clears the vision and makes the hair sprout.
Grade: Sahih

Hadith #3898 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي (Sunan Abi Dawud)
A man from Aslam tribe said: I was sitting with the Messenger of Allah (ﷺ). A man from among his Companions came and said: Messenger of Allah! I have been stung last night, and I could not sleep till morning. He asked: What was that? He replied: A scorpion. He said: Oh, had you said in the evening: “I take refuge in the perfect words of Allah from the evil of what He created,” nothing would have harmed you, Allah willing.
Grade: Sahih

Hadith #3903 - Sunan Abi Dawud - Abu Hurairah; Hammad bin Salama حماد بن سلمة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hkym al-Athrm al-Bsry حكيم الأثرم البصري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
My mother intended to make me gain weight to send me to the (house of) the Messenger of Allah (ﷺ). But nothing which she desired benefited me till she gave me cucumber with fresh dates to eat. Then I gained as much weight (as she desired).
Grade: Sahih

Hadith #3910 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hassan ibn Ali bin Abi Talib; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Taking omens is polytheism; taking omens is polytheism. He said it three times. Every one of us has some, but Allah removes it by trust (in Him).
Grade: Sahih

Hadith #3911 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying : There is no infection, no evil, omen or serpent, in a hungry belly and no hamah. A nomadic Arab asked: How is it that when camels are in the sand as if they were gazelles and a mangy camel comes among them and it gives them mange ? He replied: Who infected the first one ? Ma’mar, quoting al-Zuhri said: A man told me that Abu Hurairah narrated to him saying that he heard the Prophet (ﷺ) say: A diseased camel should not be brought with a healthy camel t
Grade: Sahih

Hadith #3912 - Sunan Abi Dawud - Abu Hurairah; al-Q'qa' bin Hkym al-Knany القعقاع بن حكيم الكناني المدني; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin 'Abdul Rahim bin Abi Zuhayr محمد بن عبد الرحيم بن أبي زهير البزاز; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Maryam سعيد بن أبي مريم; Ubaidullah bin Mqsm عبيد الله بن مقسم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: There is no infection, no hamah, no other promising rain, and no serpent in a hungry belly.
Grade: Sahih

Hadith #3916 - Sunan Abi Dawud - Abu Hurairah; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: There is no infection* and no evil omen, and I like a good omen. Good omen means a good word. * The majority of scholars interpret this to mean that these things in and of themselves do not transmit or cause harm through supernatural or hidden means but that Allah is ultimately in control and any fearful superstition around these is false.
Grade: Sahih

Hadith #3933 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Qatada قتادة (Sunan Abi Dawud)
On his father’s authority (this is AbulWalid’s version): A man emancipated a share in a slave and the matter was mentioned to the Prophet (ﷺ). He said: Allah has no partner. Ibn Kathir added in his version: The Prophet (ﷺ) allowed his emancipation.
Grade: Sahih

Hadith #3936 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Bashayr bin Nahayk بشير بن نهيك السدوسي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي; Qatada قتادة (Sunan Abi Dawud)
If anyone emancipates his share in a slave, he emancipates him (completely) by his property if he has property. The narrator Ibn al-Muthanna did not mention al-Nadr b. Anas. This is the version of Ibn Suwaid.
Grade: Sahih

Hadith #3937 - Sunan Abi Dawud - Abu Hurairah; al-Nadr bin Anas bin Malik النضر بن أنس بن مالك الأنصاري; Ali bin al-Madini علي بن المديني; Bashayr bin Nahayk بشير بن نهيك السدوسي; Muhammad bin Bashr bin al-Farafsa محمد بن بشر بن الفرافصة العبدي; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
If anyone emancipates a share in his slave, he should completely emancipate him if he has money; but if he has none, then slave will be required to work (to pay for his freedom), but he must not be overburdened.
Grade: Sahih

Hadith #3962 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
If anyone emancipates a slave who has property, the property of the slave belongs to him except that the master makes a stipulation.
Grade: Sahih

Hadith #3988 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ikrama عكرمة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I came to the Prophet (ﷺ). He then narrated the rest of the tradition. A man from the people said: “Messenger of Allah! tell us about Saba’; what is it: land or woman? He replied: It is neither land nor woman; it is a man to whom ten children of the Arabs were born: six of them lived in the Yemen and four lived in Syria. The narrator Uthman said al-Ghatafani instead of al-Ghutayfi. He said: It has been transmitted to us by al-Hasan ibn al-Hakam an-Nakha’i.
Grade: Hasan Sahih

Hadith #4018 - Sunan Abi Dawud - Abu Hurairah; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Sa'id bin Iyas al-Jariri سعيد بن إياس الجريري (Sunan Abi Dawud)
The Prophet (ﷺ) said: A man should not look at the private parts of another man, and a woman should not look at the private parts of another woman. A man should not lie with another man without wearing lower garment under one cover; and a woman should not be lie with another woman without wearing lower garment under one cover.
Grade: Sahih

Hadith #4079 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) put a turban on me and let the ends hang in front of him and behind me.
Grade: Da'if

Hadith #4085 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Abu Hurairah; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone trails his garment arrogantly, Allah will not look at him on the Day of Resurrection. Then Abu Bakr said: One of the sides of my lower garment trails, but still I remain careful about it. He said: You are not one of those who do so conceitedly.
Grade: Sahih

Hadith #4089 - Sunan Abi Dawud - Abu Hurairah; Ata'a bin al-Sa'ib al-Thaqifi عطاء بن السائب الثقفي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Salman al-Aghar Abu 'Abdullah سلمان الأغر أبو عبد الله (Sunan Abi Dawud)
My father told me that he was a companion of Abu Darda’. There was in Damascus a man from the companions of the Prophet (ﷺ), called Ibn al-Hanzaliyyah. He was a recluse and rarely met the people. He remained engaged in prayer. When he was not praying he was occupied in glorifying Allah and exalting Him until he went to his family. Once he passed us when we were with AbudDarda’. AbudDarda’ said to him: Tell us a word which benefits us and does not harm you. He said: The Messenger of Allah
Grade: Hasan

Hadith #4091 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: He who has in his heart as much pride as much pride as grain of mustard-seed will not enter paradise. And he who has in his heart as much faith as grain of mustard-seed will not enter Hell. Abu Dawud said: Al-Qasmali has transmitted it from Al-A’mash in a similar way.
Grade: Sahih

Hadith #4097 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Hurairah; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Zuhayr bin Harb زهير بن حرب بن شداد أبو خثيمة (Sunan Abi Dawud)
The Prophet (ﷺ) cursed women who imitate men and men who imitate women.
Grade: Sahih

Hadith #4129 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Imran bin Husain; Muhammad bin Bashar Bindar محمد بن بشار بندار; Qatada قتادة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Do not ride on silk stuff and panther skins. AbuSa’id said to us: AbuDawud said to us: The name of AbulMu’tamir is Yazid ibn Tahman. He lived in al-Hirah.
Grade: Sahih

Hadith #4135 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade that a man should put on sandals while standing.
Grade: Sahih

Hadith #4138 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
It is part of the Sunnah that when a man sits down, he should take off his sandals and place them at his side.
Grade: Da'if

Hadith #4140 - Sunan Abi Dawud - Abu Hurairah; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) liked to begin with the right side as far as possible in all conditions: in his purification, and combing. The narrator Muslim added: “in using tooth-stick,” and he did not mention “in all his conditions”. Abu Dawud said: Shu’bah transmitted it from Mu’adh, but did not mention “his tooth-stick.”
Grade: Sahih

Hadith #4157 - Sunan Abi Dawud - Abu Hurairah; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Mujahid bin Jabir مجاهد بن جبر; Yonus bin Abi Ishaq يونس بن أبي إسحاق (Sunan Abi Dawud)
Maimunah, wife of the Prophet (ﷺ) reported him as saying: Gabriel (peace be upon him) promised to visit me last night, but he did not visit me. Then it occurred to him that there was a pup under his bed. So he ordered and it was turned out. He then got water in his hand and sprinkled it on its place. When Gabriel (ﷺ) met him, he said: We do not enter a house which contains a dog or a picture. When the morning came, the Prophet (ﷺ) ordered to kill dogs. He ordered to kill the dog which guar
Grade: Sahih

Hadith #4162 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Abi al-Zanad عبد الرحمن بن أبي الزناد; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Suhayl bin Abi Salah سهيل بن أبي صالح; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
The Prophet (ﷺ) had sikkah with which he perfumed himself.
Grade: Sahih

Hadith #4171 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; Hassan ibn Ali bin Abi Talib; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Ubaidullah bin Abi Ja'far عبيد الله بن أبي جعفر المصري (Sunan Abi Dawud)
There is no harm in fastening the hair with silk or woollen threads. Abu Dawud said: It appears that he held the view that what is prohibited is the adding of the hair of women. Abu Dawud said: Ahmad (b. hanbal) used to say: There is no harm in tying the hair with silk or woollen threads.
Grade: Da'if

Hadith #4173 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a woman uses perfume and passes the people so that they may get its odour, she is so-and-so, meaning severe remarks.
Grade: Hasan

Hadith #4174 - Sunan Abi Dawud - Abu Hurairah; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Basr bin Sa'id al-Madni بسر بن سعيد المدني العابد; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Yazid bin 'Abdullah bin Khusayfa يزيد بن عبد الله بن خصيفة (Sunan Abi Dawud)
A woman met him and he found the odour of perfume in her. Her clothes were fluttering in the air. He said: O maid-servant of the Almighty, are you coming from the mosque? She replied: Yes. He said: For it did you use perfume? She replied: Yes. He said: I heard my beloved AbulQasim (ﷺ) say: The prayer of a woman who uses perfume for this mosque is not accepted until she returns and takes a bath like that of sexual defilement (perfectly). Abu Dawud said: Al-i’sar means dust.
Grade: Sahih

Hadith #4235 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Usayd bin Abi Usayd أسيد بن أبي أسيد البراد (Sunan Abi Dawud)
The Prophet (ﷺ) got some ornaments presented by Negus as a gift to him. They contained a gold ring with an Abyssinian stone. The Messenger of Allah (ﷺ) turning his attention from it took it by means of a stick or his finger, then called Umamah, daughter of Abul’As and daughter of his daughter Zaynab, and said: Wear it, my dear daughter.
Grade: Hasan

Hadith #4248 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام (Sunan Abi Dawud)
The Prophet (ﷺ) as saying: If a man takes an oath of allegiance to a leader, and puts his hand on his hand and does it with the sincerity of his heart, he should obey him as much as possible. If another man comes and contests him, then behead the other one. The narrator ‘Abd al-Rahman said: I asked: Have you heard this from the Messenger of Allah ? He said: My ears heard it and my heart retained it. I said: Your cousin Mu’awiyah orders us that we should do this and do that. He replied: Obe
Grade: Sahih

Hadith #4254 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Humaid bin 'Abdur Rahman حميد بن عبد الرحمن بن عوف الزهرى; Unbasa bin Sa'id bin al-Aas عنبسة بن سعيد بن العاص بن سعيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: The mill of Islam will go round till the year thirty-five, or thirty-six, or thirty-seven; then if they perish, they will have followed the path of those who perished before them, but if their religion is maintained, it will be maintained for seventy years. I asked: Does it mean seventy years which remain or seventy years which are gone by? He replied: It means (seventy years) that are gone by. Abu Dawud said: Those who recorded Khirash, the name of a narrator, are wrong.
Grade: Sahih

Hadith #4263 - Sunan Abi Dawud - Abdul Malik bin Shu'aib bin al-Laith عبد الملك بن شعيب بن الليث بن سعد; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Khalid bin Abi 'Imran خالد بن أبي عمران; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Abi Dawud)
I swear by Allah, I heard the Messenger of Allah (ﷺ) say: The happy man is he who avoids dissensions: happy is the man who avoids dissensions; happy is the man who avoids dissensions: but how fine is the man who is afflicted and shows endurance.
Grade: Sahih

Hadith #4301 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah will not gather two swords upon this community: Its own sword and the sword of its enemy.
Grade: Sahih

Hadith #4310 - Sunan Abi Dawud - Abu Hurairah; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Ahmed bin 'Abdullah أحمد بن عبد الله بن أبي; Ammara bin al-Q'aqa' bin Shabrma عمارة بن القعقاع بن شبرمة (Sunan Abi Dawud)
A group of people came to Marwan in Medina, and they heard him say that the first of the signs to appear would be the coming forth of the Dajjal (Antichirst). He said: I then went to Abd Allah b. ‘Amr and mentioned it to him. He did not say anything(reliable). I heard the Messenger of Allah (ﷺ) say: The first of the signs to appear will be the rising of the sun in its place of setting and the coming forth of the beast against mankind in the forenoon. Whichever of them comes first will soon b
Grade: Sahih

Hadith #4311 - Sunan Abi Dawud - Abdullah bin Sa'id al-Ashaj عبد الله بن سعيد بن حصين الكندي - الأشج; Abu Hurairah; Hafs bin 'Asim bin 'Umar حفص بن عاصم بن عمر; Khbyb bin 'Abdur Rahman خبيب بن عبد الرحمن بن خبيب; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uqba bin Khalid bin 'Uqba - al-Majdar عقبة بن خالد بن عقبة السكوني المجدر (Sunan Abi Dawud)
We were sitting in the shade of the chamber of the Messenger of Allah (ﷺ) discussing (something) and when we mentioned the last hour, our voices rose high. The Messenger of Allah (ﷺ) said: The last hour will not come or happen until there appear ten signs before it : the rising of the sun in its place of setting, the coming forth of the beast, the coming forth of Gog and Magog, the Dajjal (Antichrist), (the descent of) Jesus son of Mary, the smoke, and three collapses of the earth: one in th
Grade: Sahih

Hadith #4312 - Sunan Abi Dawud - Abdullah bin Sa'id al-Ashaj عبد الله بن سعيد بن حصين الكندي - الأشج; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Uqba bin Khalid bin 'Uqba - al-Majdar عقبة بن خالد بن عقبة السكوني المجدر (Sunan Abi Dawud)
The last hour will not come before rising of the sun in its place of setting. When it rises (there) and the people see it, those who are on it (the earth) will believe. This is the time of which the Qur’anic verse says: “. . .no good will it do to a soul to believe in them then, if it believed not before nor earned righteousness through its faith.”
Grade: Sahih

Hadith #4322 - Sunan Abi Dawud - Abu Hurairah; Hadba bin Khalid bin al-Aswad هدبة بن خالد بن الأسود; Hmam bin Yahya bin Dinar همام بن يحيى بن دينار; Qatada قتادة (Sunan Abi Dawud)
A similar tradition has been transmitted by Abu Umamah from the prophet (ﷺ) through a different chain of narrators. In this version he mentioned the prayers to the same effect.
Grade: Sahih

Hadith #4331 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
You swear by Allah! He said: I heard Umar swearing to that in the presence of the Messenger of Allah (ﷺ), but the Messenger of Allah (ﷺ) did not make any objection to it.
Grade: Sahih

Hadith #4332 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
We saw the last of Ibn Sayyad at the battle of the Harrah.
Grade: Sahih

Hadith #4410 - Sunan Abi Dawud - Abu Hurairah; Abu Salamah; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Umar bin Abi Salamah; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
A thief was brought to the Prophet (ﷺ). He said: Kill him. The people said: He has committed theft, Messenger of Allah! Then he said: Cut off his hand. So his (right) hand was cut off. He was brought a second time and he said: Kill him. The people said: He has committed theft, Messenger of Allah! Then he said: Cut off his foot. So his (left) foot was cut off. He was brought a third time and he said: Kill him. The people said: He has committed theft, Messenger of Allah! So he said: Cut off his
Grade: Hasan

Hadith #4426 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ibn Jurayj ابن جريج; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Abi Dawud)
Ma’iz ibn Malik came to the Prophet (ﷺ) and admitted fornication twice. But he drove him away. He then came and admitted fornication twice. But he drove him away. He then came and admitted fornication twice. He (the Prophet) said: You have testified to yourself four times. Take him away and stone him to death.
Grade: Sahih

Hadith #4443 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
I heard an old man who transmitted from Abu Bakrah on this father’s authority that the Prophet (ﷺ) had a woman stoned and a pit was dug up to her breasts. Abu Dawud said: A man made me understand it from ‘Uthman (b. Abi Shaibah) Abu Dawud said: Al-Ghassani said: Juhainah, Ghamid and Bariq as the same.
Grade: Sahih

Hadith #4448 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Muhammad Ibn Maslama; Unbasa bin Sa'id bin al-Aas عنبسة بن سعيد بن العاص بن سعيد; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The people passed by the Messenger of Allah (ﷺ) with a Jew who was blackened with charcoal and who was being flogged. He called them and said: Is this the prescribed punishment for a fornicator? They said: Yes. He then called on a learned man among them and asked him: I adjure you by Allah Who revealed the Torah to Moses, do you find this prescribed punishment for a fornicator in your divine Book? He said: By Allah, no. If you had not adjured me about this, I should not have informed you. We f
Grade: Sahih

Hadith #4449 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
A group of Jews came and invited the Messenger of Allah (ﷺ) to Quff. So he visited them in their school. They said: AbulQasim, one of our men has committed fornication with a woman; so pronounce judgment upon them. They placed a cushion for the Messenger of Allah (ﷺ) who sat on it and said: Bring the Torah. It was then brought. He then withdrew the cushion from beneath him and placed the Torah on it saying: I believed in thee and in Him Who revealed thee. He then said: Bring me one who is le
Grade: Hasan

Hadith #4467 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود; Zayd bin Khalid al-Juhni (Sunan Abi Dawud)
A man of Bakr ibn Layth came to the Prophet (ﷺ) and made confession four times that he had committed fornication with a woman, so he had a hundred lashes administered to him. The man had not been married. He then asked him to produce proof against the woman, and she said: I swear by Allah, Messenger of Allah, that he has lied. Then he was given the punishment of eighty lashes of falsehood.
Grade: Da'if

Hadith #4468 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and said: I contacted directly a women at the furthest part of the city (i.e., Medina), and I did with her everything except sexual intercourse. So here I am; inflict any punishment you wish. Thereupon ‘Umar said: Allah has concealed your fault; it would have been better if you also had concealed it yourself. The Prophet (ﷺ) sent a men after him. (When he came) he recited the verse: “And establish regular prayers at the two ends of the day and at the approac
Grade: Hasan Sahih

Hadith #4469 - Sunan Abi Dawud - Abu Hurairah; Ibn Ishaq محمد بن إسحاق بن يسار‎; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) was asked about a slave-woman who commits fornication, and she is not married: If she commits fornication, flog her: if she commits fornication again flog her; if only for a rope of hair (dafir). Ibn Shihab: I do not know whether he (the Prophet) said it is a third or a fourth time.
Grade: Sahih

Hadith #4475 - Sunan Abi Dawud - Abu Damra, Anas bin 'Ayyad أنس بن عياض الليثي - أبو ضمرة; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
He (the Prophet) commanded regarding the two men and the woman who spoke obscenity were Hassan ibn Thabit and Mistah ibn Uthathah. An-Nufayl said: It is said that the woman was Hammah daughter of Jahsh.
Grade: Hasan

Hadith #4482 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Nsr bin 'Asim al-Antaky نصر بن عاصم الأنطاكي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: If they (the people) drink wine, flog them, again if they drink it, flog them. Again if they drink it, kill them.
Grade: Hasan Sahih

Hadith #4491 - Sunan Abi Dawud - Abu Hurairah; Abu Salamah; Fdyl bin Husayn bin Talha فضيل بن حسين بن طلحة; Umar bin Abi Salamah; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
No more than ten lashes are to be given, except in the case of one of the punishment prescribed by Allah, the Exalted.
Grade: Sahih

Hadith #4496 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
The Prophet (ﷺ) said: If a relative of anyone is killed, or if he suffers khabl, which means a wound, he may choose one of the three things: he may retaliate, or forgive, or receive compensation. But if he wishes a fourth (i.e. something more), hold his hands. After this whoever exceeds the limits shall be in grave penalty.
Grade: Da'if

Hadith #4507 - Sunan Abi Dawud - Aabad bin al-Wam bin عباد بن العوام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Da'ud bin Rshyd داود بن رشيد; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Sa'id bin Abi Sa'id; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sufyan bin Hussain bin al-Hasan سفيان بن حسين السلمي (Sunan Abi Dawud)
The Prophet (ﷺ) said: I will not forgive anyone who kills after accepting blood-wit
Grade: Da'if

Hadith #4510 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
Jabir ibn Abdullah used to say that a Jewess from the inhabitants of Khaybar poisoned a roasted sheep and presented it to the Messenger of Allah (ﷺ) who took its foreleg and ate from it. A group of his companions also ate with him. The Messenger of Allah (ﷺ) then said: Take your hands away (from the food). The Messenger of Allah (ﷺ) then sent someone to the Jewess and he called her. He said to her: Have you poisoned this sheep? The Jewess replied: Who has informed you? He said: This forele
Grade: Da'if

Hadith #4530 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu Hurairah; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'd ibn 'Ubadah (Sunan Abi Dawud)
I and Ashtar went to Ali and said to him: Did the Messenger of Allah (ﷺ) give you any instruction about anything for which he did not give any instruction to the people in general? He said: No, except what is contained in this document of mine. Musaddad said: He then took out a document. Ahmad said: A document from the sheath of his sword. It contained: The lives of all Muslims are equal; they are one hand against others; the lowliest of them can guarantee their protection. Beware, a Muslim mu
Grade: Sahih

Hadith #4531 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'd ibn 'Ubadah; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
On his father’s authority, said that his grandfather reported the Messenger of Allah (ﷺ) said, mentioning the tradition similar to the one transmitted by Ali. This version adds: The most distant of them gives protection as from all, those who are strong among them send back (spoil) to those who are weak among them, and their expeditions sending it back to those who are at home.
Grade: Hasan Sahih

Hadith #4574 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Wahb bin Bayan وهب بن بيان; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
About the story of Haml ibn Malik, Ibn Abbas said: She aborted a child who had grown hair and was dead, and the woman also died. He (the Prophet) gave judgment that the blood-wit was to be paid by the woman’s relatives on the father’s side. Her uncle said: Messenger of Allah! She has aborted a child who had grown hair. The father of the woman who had slain said: He is a liar: I swear by Allah, he did not raise his voice, or drink or eat. No compensation is to be paid for an offence like this
Grade: Da'if

Hadith #4577 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة (Sunan Abi Dawud)
About this story: Then the woman, against whom he decided that a male or female should be paid for her, died. The Messenger of Allah (ﷺ) then gave judgement that her sons will inherit from her, and the bloodwit should be paid by her relatives on the father’s side.
Grade: Sahih

Hadith #4590 - Sunan Abi Dawud - Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin Sa'id bin Yazid محمد بن سعيد بن يزيد بن إبراهيم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Hussain bin al-Hasan سفيان بن حسين السلمي; Uthman bin Muhammad (Sunan Abi Dawud)
A servant of some poor people cut off the ear of the servant of some rich people. His people came to the Prophet (ﷺ) and said: Messenger of Allah! we are poor people. So he imposed no compensation on them.
Grade: Sahih

Hadith #4591 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone is killed blindly or, when people are throwing stones, by a stone or a whip, his blood-wit is the blood-wit for an accidental murder. But if anyone is killed intentionally, retaliation is due. If anyone tries to prevent it, the curse of Allah, of angels, and of all the people will rest on him.
Grade: Sahih

Hadith #4592 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Hamam bin Munabbih همام بن منبه بن كامل; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
The Prophet (ﷺ) said: No recompense is to be demanded if one is kicked by an animal. Abu Dawud said: An animal kicks someone with its leg while one is riding on it.
Grade: Da'if

Hadith #4594 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
The Prophet (ﷺ) said: No recompense may be demanded if the fire spreads.
Grade: Sahih

Hadith #4601 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
I came to my family when my hands had cracks. They dyed me with saffron. I then went to Prophet (ﷺ) and saluted him, but he did not return me salutation. He said: Go and wash it away from you.
Grade: Hasan

Hadith #4607 - Sunan Abi Dawud - Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Yahya bin Ayoub al-Maqabri يحيى بن أيوب المقابري (Sunan Abi Dawud)
AbdurRahman ibn Amr as-Sulami and Hujr ibn Hujr said: We came to Irbad ibn Sariyah who was among those about whom the following verse was revealed: “Nor (is there blame) on those who come to thee to be provided with mounts, and when thou saidst: “I can find no mounts for you.” We greeted him and said: We have come to see you to give healing and obtain benefit from you. Al-Irbad said: One day the Messenger of Allah (ﷺ) led us in prayer, then faced us and gave us a lengthy exhortation at w
Grade: Sahih

Hadith #4630 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Abi Dawud)
I heard Sufyan say: If anyone thinks that ‘All (Allah be pleased with him) was more deserving for the Caliphate than both of them, he imputed error to Abu Bakr, ‘Umar, the Muhajirun (Immigrants), and the Ansar (Helpers) Allah be pleased with all of them. I think that with this (belief) none of his action will rise to the heaven.
Grade: Sahih

Hadith #4650 - Sunan Abi Dawud - Abdul Salam bin Harb bin Salm al-Mala'i عبد السلام بن حرب بن سلم النهدي الملائي; Abdur Rahman bin Muhammad al-Maharbi عبد الرحمن بن محمد بن زياد المحاربي; Abu Hurairah; Abu Khalid al-Dalani أبو خالد الدالاني الأسدي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب (Sunan Abi Dawud)
I was sitting with someone in the mosque of Kufah while the people of Kufah were with him. Then Sa’id ibn Zayd ibn Amr ibn Nufayl came and he welcomed him, greeted him, and seated him near his foot on the throne. Then a man of the inhabitants of Kufah, called Qays ibn Alqamah, came. He received him and began to abuse him. Sa’id asked: Whom is this man abusing? He replied: He is abusing Ali. He said: Don’t I see that the companions of the Messenger of Allah (ﷺ) are being abused, but you n
Grade: Sahih

Hadith #4652 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin Snan bin Asad أحمد بن سنان بن أسد; Asim al-Ahwal عاصم الأحول; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Salama حماد بن سلمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: Gabriel came and taking me by the hand showed the gate of Paradise by which my people will enter. AbuBakr then said: Messenger of Allah! I wish I had been with you so that I might have looked at it. The Messenger of Allah (ﷺ) then said: You, AbuBakr, will be the first of my people to enter Paradise.
Grade: Da'if

Hadith #4669 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan Abi Dawud)
It is not fitting for a servent to say that I (The Prophet) is better than Jonah son of Matta.
Grade: Sahih

Hadith #4671 - Sunan Abi Dawud - Abdullah bin Farroukh al-Khurasni عبد الله بن فروخ الخراساني; Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Amr bin 'Uthman عمرو بن عثمان بن عفان (Sunan Abi Dawud)
A man from among the Jews said : By him who chose Moses above the universe. So a Muslim raised his hand and slapped the Jew on his face. The Jew went to the Messenger of Allah (May peace be upon him) and informed him. The Prophet (May peace be upon him) said: Do not make me superior to Moses, for mankind (on the Day of Resurrection) will swoon and I will be the know whether he was among those who swooned and had recovered before me, or he was among those of whom Allah had made an exception. Abu
Grade: Sahih

Hadith #4672 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ma'mar bin Rashid معمر بن راشد; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Muhammad bin Abi Sari محمد بن أبي السري; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
A man said to the Messenger of Allah (May peace be upon him): O best of all creatures! The Messenger of Allah (May peace be upon him) said : That was Abraham (peace be upon him).
Grade: Sahih

Hadith #4673 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
I shall be pre-eminent among the descendants of Adam, the first from whom the earth will be cleft open the first intercessor, and the first whose intercession will be accepted.
Grade: Sahih

Hadith #4674 - Sunan Abi Dawud - Abdullah bin Dinar عبد الله بن دينار العدوي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
I do not know whether Tubba was accursed or not, and ‘Uzair (Azra was a prophet or not).
Grade: Sahih

Hadith #4680 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmad bin Hanbal أحمد بن حنبل; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
when the Prophet (May peace be upon him) turned towards the Ka’bah (in prayer), the people asked : Messenger of Allah (May peace be upon him)! what will happen with those who died while they prayed with their faces towards Jerusalem ? Allah the Exalted, then revealed : “And never would Allah make your faith of no effect.”
Grade: Sahih

Hadith #4687 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Ibrahim bin Muhammad bin al-Harith إبراهيم بن محمد أبو اسحاق الفزاري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
If any believing man calls another believing man an unbeliever, if he is actually an infidel, it is all right ; if not, he will become an infidel.
Grade: Sahih

Hadith #4688 - Sunan Abi Dawud - Abu Hurairah; Ishaq bin Ibrahim bin Swyd إسحاق بن إبراهيم بن سويد; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Sa'id bin Abi Maryam سعيد بن أبي مريم; Sa'id bin Abi Sa'id; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
Four characteristics constitute anyone who possesses them a sheer hypocrite, and anyone who possesses one of them possesses a characteristics of hypocrisy till he abandons it : when he talks he lies, when he makes a promise he violates it, when he makes a covenant he acts treacherously, and when he quarrels, he deviates from the Truth.
Grade: Sahih

Hadith #4696 - Sunan Abi Dawud - Abu Dharr al-Ghaffari; Abu Hurairah; Abu Zara' bin 'Amr /Harm أبو زرعة بن عمرو/هرم; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Uthman bin Muhammad (Sunan Abi Dawud)
we met ‘Abd Allah b. ‘Umar. We told him about divine decree and what they said about it. He then mentioned something similar to it. He added : A man of Muzainah or juhainah asked : What is the good in doing anything, Messenger of Allah ? should we think that a thing has passed and gone or a thing that has happened now (without predestination)? He replied : About a thing that has passed and gone (i.e. predestined). A man or some people asked: Then, why action? He replied: Those who are among
Grade: Sahih

Hadith #4708 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Ata'a bin Dinar al-Hdhly عطاء بن دينار الهذلي مولاهم; Hakeem bin Sharik al-Hadhli حكيم بن شريك الهذلي; Rabi'yah al-Jrshy ربيعة الجرشي; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Umar ibn al-Khattab; Yahya bin Maymun al-Hdrmy يحيى بن ميمون الحضرمي (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) who spoke the truth and whose word was belief told us the following : The constituents of one of you are collected for forty days in his mother’s womb, then they become a piece of congealed blood for a similar period, then they become a lump of flesh for a similar period. Then Allah sends to him an angel with four words who records his provision the period of his life, his deeds, and whether he will be miserable or blessed ; thereafter he breathe
Grade: Sahih

Hadith #4712 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
I said : Messenger of Allah (May peace be upon him) what happens to the offspring of believers ? He replied : They are joined to their parents. I asked : Messenger of Allah! Although they have done nothing ? He replied : Allah knows best what they were doing. I asked : what happens to the offspring of polytheists, Messenger of Allah ? he replied! They are joined to their parents. I asked : Although they have done nothing? He replied : Allah knows best what they were doing.
Grade: Sahih

Hadith #4718 - Sunan Abi Dawud - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Ata'a bin Dinar al-Hdhly عطاء بن دينار الهذلي مولاهم; Hakeem bin Sharik al-Hadhli حكيم بن شريك الهذلي; Rabi'yah al-Jrshy ربيعة الجرشي; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Umar ibn al-Khattab (Sunan Abi Dawud)
A man asked : where is my father, Messenger of Allah? He replied! Your father is in Hell. When he turned his back, he said : My father and your father are in Hell.
Grade: Sahih

Hadith #4719 - Sunan Abi Dawud - Abu Hurairah; Harun bin al-Ma'ruf هارون بن معروف المروزي الخزاز الضرير; Hisham bin 'Urwa هشام بن عروة; Sufyan bin 'Uyaynah سفيان بن عيينة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The devil flows in a man like his blood.
Grade: Sahih

Hadith #4720 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Salmah bin al-Fadl al-Abrash سلمة بن الفضل الأبرش; Utba bin Muslim al-Madni عتبة بن مسلم المدني (Sunan Abi Dawud)
Do not sit with those who believe in free will and do not address them before they address you.
Grade: Da'if

Hadith #4728 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
I heard Abu Hurairah recite this verse : “Allah doth command you to render back your trusts to those to whom they are due” up to “For Allah is he who heareth and seeth all things”. He said : I saw the Messenger of Allah (May peace be upon him) putting his thumb on his ear and finger on his eye. Abu Hurairah said : I saw the Messenger of Allah (May peace be upon him) reciting this verse and putting his fingers. Ibn Yunus said that al-Muqri said. “Allah hears and sees” means that Allah
Grade: Sahih

Hadith #4731 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Salman al-Aghar Abu 'Abdullah سلمان الأغر أبو عبد الله (Sunan Abi Dawud)
I asked: Messenger of Allah! will each one of us see his Lord? Ibn Mu’adh’s version has: “being alone with Him, on the Day of Resurrection? And what sign is there is His creation?” He replied: AbuRazin! does each one of you not see the moon? Ibn Mu’adh’s version has: “on the night when it is full, being alone with it?” Then the agreed version goes: I said: Yes. He said: Allah is more great. Ibn Mu’adh’s version has: It is only part of Allah’s creation, but Allah is more gl
Grade: Hasan

Hadith #4741 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
I heard the Prophet(ﷺ) say: Those who go to Paradise will eat in it and drink.
Grade: Sahih

Hadith #4742 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: The trumpet (sur) which will be blown.
Grade: Sahih

Hadith #4788 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Bashr bin Rafa'i al-Harithy بشر بن رافع الحارثي; Hjaj bin Frafs'h حجاج بن فرافصة الباهلي; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Muhammad bin Abi Sari محمد بن أبي السري; Nasr bin 'Ali bin Nasr bin 'Ali; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Abi Dawud)
When the Prophet (ﷺ) was informed of anything of a certain man, he would not say: What is the matter with so and so that he says? But he would say: What is the matter with the people that they say such and such?
Grade: Sahih

Hadith #4809 - Sunan Abi Dawud - Abu Hurairah; al-Rabi' bin Muslim al-Jmhy Abu الربيع بن مسلم الجمحي; Muhammad bin Ziyad محمد بن زياد القرشي; Muslim bin Ibrahim al-Azdy مسلم بن إبراهيم الأزدي الفراهيدي (Sunan Abi Dawud)
The Prophet (ﷺ) said: He who is deprived of gentleness is deprived of good.
Grade: Sahih

Hadith #4814 - Sunan Abi Dawud - Abdur Rahman bin Ishaq عبد الرحمن بن إسحاق بن عبد الله; Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: If someone is donated something, and he mentions it, he thanks for it, and if he conceals it, he is ungrateful for it.
Grade: Sahih

Hadith #4819 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
A woman who had something (feebleness) in her mind.
Grade: Sahih

Hadith #4831 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Da'ud أبو داود السجستاني الأزدي; Abu Hurairah; Muhammad bin Bashar Bindar محمد بن بشار بندار; Zuhayr bin Muhammad al-Tamimi زهير بن محمد التميمي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Anas b. Malik from the Prophet (ﷺ) through a different chain of narrators in a similar way.
Grade: Sahih

Hadith #4838 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Qurrah bin Khalid al-Sadusi قرة بن خالد السدوسي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) spoke in a distinct and leisurely manner.
Grade: Sahih

Hadith #4839 - Sunan Abi Dawud - Abdul Wahid bin Ziyad عبد الواحد بن زياد العبدي; Abu Hurairah; Asim bin Kulayb bin Shahab عاصم بن كليب بن شهاب بن المجنون; Kulayb bin Shahab كليب بن شهاب; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) spoke in a distinct manner so that anyone who listened to him could understand it.
Grade: Hasan Sahih

Hadith #4851 - Sunan Abi Dawud - Abu Hurairah; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
Two persons should not talk privately ignoring the third, for that will grieve him.
Grade: Sahih

Hadith #4853 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Isma'il bin Zakaria bin Mrh إسماعيل بن زكريا بن مرة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
I was sitting with my father and there was also a boy with him. He got up and then returned. So my father mentioned a tradition on the authority of Abu Hurairah from the Prophet (ﷺ) saying: If anyone gets up from where he has been sitting and comes back to it, he has most right to it.
Grade: Sahih

Hadith #4854 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) would sit and we would also sit around him. If he got up intending to return, he would take off his sandals or something he was wearing, and his Companions recognising his purpose (that he would return) would stay where they were.
Grade: Da'if

Hadith #4856 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone sits at a place where he does not remember Allah, deprivation will descend on him from Allah; and if he lies at a place where he does not remember Allah, deprivation will descend on him from Allah.
Grade: Hasan Sahih

Hadith #4860 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Aqil bin Khalid bin 'Aqil عقيل بن خالد بن عقيل الأيلي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
The Prophet (ﷺ) said: None of my Companions must tell me anything about anyone, for I like to come out to you with no ill-feelings.
Grade: Da'if

Hadith #4870 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The most serious breach of trust in Allah’s sight is that a man who has intercourse with his wife, and she with him, spreads her secret.
Grade: Da'if

Hadith #4872 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
The worst of the people is a man who is double-faced; he presents one face to some and another to others.
Grade: Sahih

Hadith #4875 - Sunan Abi Dawud - Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن; Amr bin Abi Salmah عمرو بن أبي سلمة التنيسي; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
I said to the Prophet (ﷺ): It is enough for you in Safiyyah that she is such and such (the other version than Musaddad’s has:) meaning that she was short-statured. He replied; You have said a word which would change the sea if it were mixed in it. She said: I imitated a man before him (out of disgrace). He said: I do not like that I imitate anyone even if I should get such and such.
Grade: Sahih

Hadith #4880 - Sunan Abi Dawud - Abu Hurairah; Asbat bin Muhammad أسباط بن محمد; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Prophet (ﷺ) said: O community of people, who believed by their tongue, and belief did not enter their hearts, do not back-bite Muslims, and do not search for their faults, for if anyone searches for their faults, Allah will search for his fault, and if Allah searches for the fault of anyone, He disgraces him in his house.
Grade: Hasan Sahih

Hadith #4892 - Sunan Abi Dawud - Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; al-Ala' bin 'Abdur Rahman bin Ya'qub العلاء بن عبد الرحمن (Sunan Abi Dawud)
AbulHaytham quoted Dukhayn, the scribe of Uqbah ibn Amir, saying: We had some neighbours who used to drink wine. I forbade them, but they did not stop. I then said to Uqbah ibn Amir: These neighbours of ours drink wine, and I tried to prevent them but they did not stop, and I am going to call the police about them. He said: Leave them. I again came to Uqbah ibn Amir and said: Our neighbours have refused to refrain from drinking wine, and I am going to call the police for them. He said: Woe to th
Grade: Hasan

Hadith #4895 - Sunan Abi Dawud - Abdul A'ala bin Hamad bin Nasr al-Bahli عبد الأعلى بن حماد بن نصر الباهلي النرسي; Abu Hurairah; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Safwan bin 'Isa al-Zhry صفوان بن عيسى الزهري أبو محمد البصري; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Prophet (ﷺ) said: Allah has revealed to me that you must be humble, so that no one oppresses another and boasts over another.
Grade: Sahih

Hadith #4899 - Sunan Abi Dawud - Abu Hurairah; Ali bin Thabit al-Jzry علي بن ثابت الجزري أبو أحمد; Dmdm bin Jws ضمضم بن جوس; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Abi Dawud)
When your companion dies, leave him and do not revile him.
Grade: Sahih

Hadith #4901 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Hurairah; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي; Uthman bin Salah al-Sahmi عثمان بن صالح بن صفوان السهمي (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: There were two men among Banu Isra’il, who were striving for the same goal. One of them would commit sin and the other would strive to do his best in the world. The man who exerted himself in worship continued to see the other in sin. He would say: Refrain from it. One day he found him in sin and said to him: Refrain from it. He said: Leave me alone with my Lord. Have you been sent as a watchman over me? He said: I swear by Allah, Allah will not forgiv
Grade: Sahih

Hadith #4910 - Sunan Abi Dawud - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Muhammad bin Hilal bin Aby محمد بن هلال بن أبي هلال المدني; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري (Sunan Abi Dawud)
Do not hate each other; do not envy each other; do not desert each other; and be the servants of Allah as brethren. It is not allowed for a Muslim to keep apart from his brother for more than three days.
Grade: Sahih

Hadith #4912 - Sunan Abi Dawud - Abu Hurairah; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is not allowable for a believer to keep from a believer for more than three days. If three days pass, he should meet him and give him a salutation, and if he replies to it they will both have shared in the reward; but if he does not reply he will bear his sin (according to Ahmad’s version) and the one who gives the salutation will have come forth from the sin of keeping apart.
Grade: Da'if

Hadith #4914 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Suhayl bin Abi Salah سهيل بن أبي صالح; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Prophet (ﷺ) said: It is not allowable for a Muslim to keep apart from his brother for more than three days, for one who does so and dies will enter Hell.
Grade: Sahih

Hadith #4915 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر (Sunan Abi Dawud)
AbuKhirash heard the Messenger of Allah (ﷺ) say: If one keeps apart from his brother for a year, it is like shedding his blood.
Grade: Sahih

Hadith #4916 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; al-Rabi' bin Sulaiman الربيع بن سليمان; Kathir bin Zayd al-'Aslmy كثير بن زيد الأسلمي; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
The gates of Paradise are opened on Mondays and Thursdays, and forgiveness is granted to every man who does not associate anything with Allah, except for a man between whom and his brother there is rancor. Command will be given that they should be given respite till they conciliate. Abu Dawud said: The Prophet (ﷺ) kept apart from some of his wives for forty days, and Ibn ‘Umar kept apart from his son till he died. Abu Dawud said: If keeping apart is meant for the sake of Allah, then it has n
Grade: Sahih

Hadith #4926 - Sunan Abi Dawud - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hashim al-Rmany أبو هاشم الرماني; Abu Hurairah; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; al-Mfdl bin Yonus al-J'fy Abu المفضل بن يونس الجعفي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال (Sunan Abi Dawud)
When we were with Ibn ‘Umar, he heard the sound of a man who was blowing a pipe. He then mentioned a similar tradition. Abu Dawud said : This is more rejected.
Grade: Sahih

Hadith #4938 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: He who plays backgammon disobeys Allah and His Apostle.
Grade: Hasan

Hadith #4940 - Sunan Abi Dawud - Abu Hurairah; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) saw a man pursuing a pigeon. He said: A devil is pursuing a female devil.
Grade: Hasan Sahih

Hadith #4944 - Sunan Abi Dawud - Abu Bakr bin Abi Uvais أبو بكر بن أبي أويس; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
To Allah, his book, his Apostle, the leaders (public authorities) of the believers and all the believers, and the leaders (public authorities) of Muslim and the Muslims and the Muslims in general.
Grade: Sahih

Hadith #4963 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Zayd ibn Aslam quoted his father as saying: Umar ibn al-Khattab (Allah be pleased with him) struck one of his sons who was given the kunyah AbuIsa, and al-Mughirah ibn Shu’bah had the kunyah AbuIsa. Umar said to him: Is it not sufficient for you that you are called by the kunyah AbuAbdullah? He replied: The Messenger of Allah (ﷺ) gave me this kunyah. Thereupon he said: The Messenger of Allah (ﷺ) was forgiven all his sins, past and those followed. But we are among the people similar to us.
Grade: Hasan Sahih

Hadith #4972 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: it is a bad riding-beast for a man (to say) za’ama (they asserted). Abu DAwud said : This Abu ‘Abd Allah is Hudhaifah.
Grade: Sahih

Hadith #4973 - Sunan Abi Dawud - Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Habib bin al-Shaheed al-Azdi حبيب بن الشهيد الأزدي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
To proceed (amma ba’d)
Grade: Sahih

Hadith #4981 - Sunan Abi Dawud - Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
A speaker gave sermon before the prophet (May peace be upon him). He said : he who obeys Allah and his Prophet will follow the right course, and he who disobeys them. He (The prophet) said: get up; he said: go away, a bad speaker you are.
Grade: Sahih

Hadith #4990 - Sunan Abi Dawud - Abu Hurairah; Ali bin Hafs al-Mada'ini علي بن حفص المدائني; Hafs bin 'Asim bin 'Umar حفص بن عاصم بن عمر; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; Khbyb bin 'Abdur Rahman خبيب بن عبد الرحمن بن خبيب; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Woe to him who tells things, speaking falsely, to make people laugh thereby. Woe to him! Woe to him!.
Grade: Hasan

Hadith #4991 - Sunan Abi Dawud - Abu Hurairah; Hammad bin Salama حماد بن سلمة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Abi Dawud)
My mother called me one day when the Messenger of Allah (ﷺ) was sitting in our house. She said: Come here and I shall give you something. The Messenger of Allah (ﷺ) asked her: What did you intend to give him? She replied: I intended to give him some dates. The Messenger of Allah (ﷺ) said: If you were not to give him anything, a lie would be recorded against you.
Grade: Hasan

Hadith #5004 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Dhak bin Shrhbyl الضحاك بن شرحبيل; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد (Sunan Abi Dawud)
The Companions of the Prophet (ﷺ) told us that they were travelling with the Prophet (ﷺ). A man of them slept, and one of them went to the rope which he had with him. He took it, by which he was frightened. The Prophet (ﷺ) said: It is not lawful for a Muslim that he frightens a Muslim.
Grade: Sahih

Hadith #5007 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Hisham bin 'Abdul Malik al-Tayalasi هشام بن عبد الملك أبو الوليد الطيالسي; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
When two men who came from the east made a speech and the people were charmed with their eloquence, the Messenger of Allah (May peace be upon him) said: In some eloquent speech there is magic.
Grade: Sahih

Hadith #5015 - Sunan Abi Dawud - Abdullah bin Abi Talha; Abdullah bin Muslima al-Qa'nabi عبد الله بن مسلمة بن قعنب القعنبي; Abu Hurairah; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ishaq bin 'Abdullah bin Abi Talha إسحاق بن عبد الله بن أبي طلحة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to setup a pulpit in the mosque for Hassan who would stand on it and satirise those who spoke against the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) would say: The spirit of holiness (i.e. Gabriel) is with Hassan so long as he speaks in defence of the Messenger of Allah (ﷺ).
Grade: Hasan

Hadith #5017 - Sunan Abi Dawud - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Hurairah; Ayoub al-Sakhtiyani أيوب السختياني; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
When the Messenger of Allah (ﷺ) finished the dawn prayer, he would ask: Did any of you have a dream last night? And he said: All that is left of Prophecy after me is a good vision.
Grade: Sahih

Hadith #5021 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: A good vision comes from Allah and a dream (hulm) from the devil, so when one of you sees what he dislikes, he must spit on his left (three times), and seek refuge in Allah from its evil. It will then not harm him.
Grade: Sahih

Hadith #5026 - Sunan Abi Dawud - Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Sa'id bin Abi Sa'id; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
When one of you yawns, he should hold his hand over his mouth, for the devil enters.
Grade: Sahih

Hadith #5027 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted in a similar way by Suhail through a different chain of narrators. This version has; “during prayer, so he should hold as far as possible”.
Grade: Sahih

Hadith #5028 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Khshysh bin Asrm bin al-'Aswad خشيش بن أصرم بن الأسود; Ma'mar bin Rashid معمر بن راشد; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي (Sunan Abi Dawud)
Allah likes sneezing but dislikes yawning. So when one of you yawns, he should restrain it as much as possible, and should not say Ha, Ha, for that is from the devil who laughs at him.
Grade: Sahih

Hadith #5031 - Sunan Abi Dawud - Abdul 'Aziz bin 'Abdullah al-Majashun عبد العزيز بن عبد الله الماجشون; Abdullah bin Dinar عبد الله بن دينار العدوي; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
Hilal ibn Yasar said: We were with Salim ibn Ubayd when a man from among the people sneezed and said: Peace be upon you. Salim said: And upon you and your mother. Later he said: Perhaps you found something (annoying) in what I said to you. He said: I wished you would not mention my mother with good or evil. He said: I have just said to you what the Messenger of Allah (ﷺ) said. We were in the presence of the Messenger of Allah (ﷺ) when a man from among the people sneezed, saying: Peace be upo
Grade: Da'if

Hadith #5032 - Sunan Abi Dawud - Abu Hurairah; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The tradition mentioned above (No. 5013) has also been mentioned by Salim ibn Ubayd al-Ashja’i to the same effect from the Prophet (ﷺ) through a different chain of narrators.
Grade: Da'if

Hadith #5048 - Sunan Abi Dawud - Abu Hurairah; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Sa'id bin Abi Sa'id; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
when you go to your bed while you are in the state of purification. The other said: Perform ablution like the ablution for prayer. He then transmitted the tradition to the effect as Mu’tamir transmitted.
Grade: Sahih

Hadith #5049 - Sunan Abi Dawud - Abu Hurairah; Khalid bin 'Abdullah al-Tahan خالد بن عبد الله بن عبد الرحمن الطحان; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي; Wahb bin Bqyh bin 'Uthman وهب بن بقية بن عثمان (Sunan Abi Dawud)
when the prophet (May peace be upon him) lay down on his bed (at night), he would say: O Allah! In Thy name I die and live. When he awoke, he said: praise be to Allah who has given us life after causing us to die and to whom we shall be resurrected.
Grade: Sahih

Hadith #5057 - Sunan Abi Dawud - Abu Hurairah; al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to recite al-Musabbihat before going to sleep, and say: They contain a verse which is better than a thousand verses.
Grade: Hasan

Hadith #5065 - Sunan Abi Dawud - Abu Hurairah; Amr bin 'Asim al-Kalabi عمرو بن عاصم الكلابي; Hashaym bin Bashayr bin al-Qasim هشيم بن بشير بن القاسم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
The Prophet (ﷺ) said: There are two qualities or characteristics which will not be returned by any Muslim without his entering Paradise. While they are easy, those who act upon them are few. One should say: “Glory be to Allah” ten times after every prayer, “Praise be to Allah” ten times and “Allah is Most Great” ten times. That is a hundred and fifty on the tongue, but one thousand and five hundred on the scale. When he goes to bed, he should say: “Allah is Most Great” thirty-f
Grade: Sahih

Hadith #5066 - Sunan Abi Dawud - Abu Hurairah; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) got some prisoners of war (slaves). I my sister and Fatimah, daughter of the prophet (May peace be upon him), went to the prophet (May peace be upon him). We complained to him about our condition, and asked him to command for giving us some prisoners (slaves). The Messenger of Allah (May peace be upon him) said; The orphans of Badr came before you (and took the slaves). The transmitter then mentioned the story of glorifying Allah after every prayer.
Grade: Sahih

Hadith #5084 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Suhayl bin Abi Salah سهيل بن أبي صالح; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
And through the same chain of transmitters the Messenger of Allah (ﷺ) said: When one rises in the morning, one should say: “We have reached the morning, and in the morning the dominion belongs to Allah, the Lord of the universe. O Allah! I ask Thee for the good this day contains, for conquest, victory, light, blessing and guidance during it; and I seek refuge in Thee from the evil it contains and the evil contained in what comes after it.” In the evening he should say the equivalent.
Grade: Da'if

Hadith #5089 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin al-Minhal al-Darir محمد بن المنهال الضرير; Rwh bin al-Qasim al-Tmymy روح بن القاسم التميمي العنبري; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
A similar tradition has been transmitted by Aban b. ‘Uthman, from ‘Uthman, from the prophet (May peace be upon him). This version does not mention the story of paralysis.
Grade: Sahih

Hadith #5095 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmed bin Muhammad bin Musa al-Samsar أحمد بن محمد بن موسى السمسار; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Salmah bin Shbyb سلمة بن شبيب; Thabit bin Qays b. Shammas (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man goes out of his house and says: “In the name of Allah, I trust in Allah; there is no might and no power but in Allah,” the following will be said to him at that time: “You are guided, defended and protected.” The devils will go far from him and another devil will say: How can you deal with a man who has been guided, defended and protected?
Grade: Sahih

Hadith #5100 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Ja'far bin Rabi'ya bin Shrhbyl جعفر بن ربيعة بن شرحبيل; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
Because it has recently been with its Lord.
Grade: Sahih

Hadith #5109 - Sunan Abi Dawud - Abu Hurairah; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
If anyone asks you refuge for Allah’s sake give him refuge; and if anyone asks you (for something) for Allah’s sake, give him. Sahl and Sulaiman said: if anyone calls you, respond to him. The Agreed version goes; if you do not afford to compensate him, pray Allah for him until you know that you have compensated him.
Grade: Sahih

Hadith #5112 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Mua'wiya bin 'Amr bin al-Mhlb معاوية بن عمرو بن المهلب بن عمرو; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Za'ida bin Qadama al-Thaqifi زائدة بن قدامة الثقفي (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and said: Messenger of Allah! one of us has thoughts of such nature that he would rather be reduced to charcoal than speak about them. He said: Allah is Most Great, Allah is Most Great, Allah is Most Great. Praise be to Allah Who has reduced the guile of the devil to evil prompting. Ibn Qudamah said “reduced his matter” instead of “reduced his guile”. Ibn Qudamah said “reduced his matter” instead of “reduced his guile”.
Grade: Sahih

Hadith #5114 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; Kaysan Abu Sa'id al-Muqbari كيسان أبو سعيد المقبري المدني; Musa bin Mrwan موسى بن مروان; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
if a man becomes the client of any people without the permission of his patrons (i.e. those who have freed him), on him will be the curse of Allah, of angels and of all people; no obligatory or supererogatory worship will be accepted from him.
Grade: Sahih

Hadith #5126 - Sunan Abi Dawud - Abdul Malik bin 'Umayr al-Qabti عبد الملك بن عمير بن سويد القبطي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Shayban bin 'Abdur Rahman شيبان بن عبد الرحمن النحوي أبو معاوية; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Messenger of Allah! A man loves some people, but he cannot do work like their work. He replied; Yes, Abu Dharr, will be with those whom you love. Abu Dharr then repeated it. The Messenger of Allah (May peace be upon him) also repeated it.
Grade: Sahih

Hadith #5135 - Sunan Abi Dawud - Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suhayl bin Abi Salah سهيل بن أبي صالح (Sunan Abi Dawud)
Al-Ala b. al-Hadrami wrote to the prophet (May peace be upon him), and he began with his name.
Grade: Da'if

Hadith #5151 - Sunan Abi Dawud - Abu Hurairah; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني (Sunan Abi Dawud)
Gabriel kept on commending the neighbor to me so that I thought he would make him an heir.
Grade: Sahih

Hadith #5152 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Abi Sari محمد بن أبي السري (Sunan Abi Dawud)
Mujahid said that Abdullah ibn Amr slaughtered a sheep and said: Have you presented a gift from it to my neighbour, the Jew, for I heard the Messenger of Allah (ﷺ) say: Gabriel kept on commending the neighbour to me so that I thought he would make an heir?
Grade: Sahih

Hadith #5163 - Sunan Abi Dawud - Abdur Rahman bin Abi Na'm عبد الرحمن بن أبي نعم; Abu Hurairah; Fadayl bin Ghazwan bin Jarir فضيل بن غزوان; Ibrahim bin Musa al-Razi al-Fara' إبراهيم بن موسى الرازي الفراء; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Mu'ml bin al-Fadl مؤمل بن الفضل (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Treating those under one’s authority well produces prosperity, but an evil nature produces evil fortune.
Grade: Da'if

Hadith #5168 - Sunan Abi Dawud - Abdullah bin 'Isa bin 'Abdur Rahman عبد الله بن عيسى بن عبد الرحمن; Abu Hurairah; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Ammar bin Razayq عمار بن رزيق; Ikrama عكرمة; Yahya bin Y'amar يحيى بن يعمر; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
I came to Ibn ‘Umar when he set his slave free. He took a stick or something else from the earth and said; for me there is no reward even equivalent to this. I heard the Messenger of Allah (May peace be upon him) say: If anyone slaps or beats his slave the atonement due from him is to set him free.
Grade: Sahih

Hadith #5170 - Sunan Abi Dawud - Abu Hurairah; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone corrupts (instigates) the wife of a man or his slave (against him), he is not from us.
Grade: Sahih

Hadith #5171 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; al-Rabi' bin Sulaiman الربيع بن سليمان; Kathir bin 'Ubaid al-Taymi كثير بن عبيد التيمي; Sulaiman bin Bilal al-Taymi سليمان بن بلال التيمي (Sunan Abi Dawud)
A man peeped into some of the apartment of the prophet (May peace be upon him). The prophet (May peace be upon him) got up taking an arrowhead or arrowheads. He said: I can still picture myself looking at the Messenger of Allah (May peace be upon him) when he was exploring to pierce him.
Grade: Sahih

Hadith #5187 - Sunan Abi Dawud - Abu Hurairah; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Hisham bin 'Urwa هشام بن عروة; Ibn Sirin محمد بن سيرين الأنصاري; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
I knocked at the door. He asked : who is there? I replied: it is I. he said: I, as though he disapproved of it.
Grade: Sahih

Hadith #5188 - Sunan Abi Dawud - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Abu Hurairah; Abu Rafi' al-Sa'agh نفيع بن رافع أبو رافع الصائغ; al-Husain bin Mua'dh bin Khlyf الحسين بن معاذ بن خليف; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Abi Dawud)
I went out with the (Messenger of Allah (ﷺ) until I entered a garden, he said: Keep on closing the door. The door was then closed. I then said: Who is there ? He then narrated the rest of the tradition. Abu Dawud said: That is to say, the tradition of Abu Musa al-Ash’ari. In this version he said: “He then knocked at the door.”
Grade: Hasan

Hadith #5191 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Abdullah أحمد بن عبد الله بن أبي; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Abi Dawud)
Most of the people did not act upon the verse about asking permission to enter the house. I have commanded this slave-girl of mine to ask my permission to enter. Abu Dawud said: ‘Ata also transmitted it from Ibn ‘Abbas in a similar way. He commanded to act upon this.
Grade: Da'if

Hadith #5196 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Hamam bin Munabbih همام بن منبه بن كامل; Ma'mar bin Rashid معمر بن راشد (Sunan Abi Dawud)
(This version is same as previous No 5176 from the Prophet (ﷺ), adding that): Afterwards another man came and said: Peace and Allah’s mercy, blessings and forgiveness be upon you! whereupon he said: Forty. adding: Thus are excellent qualities rewarded.
Grade: Da'if

Hadith #5197 - Sunan Abi Dawud - Abu Hurairah; Ibn Jurayj ابن جريج; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Yahya bin Habib bin Arby يحيى بن حبيب بن عربي; Ziyad bin 'Alaqa زياد بن علاقة (Sunan Abi Dawud)
The Prophet (ﷺ) said: Those who are nearest to Allah are they who are first to give a salutation.
Grade: Sahih

Hadith #5198 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Maryam al-Ansari أبو مريم الأنصاري; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير (Sunan Abi Dawud)
The young should salute the old, the one who is passing by should salute the one who is sitting, and a small company should salute a large one.
Grade: Sahih

Hadith #5206 - Sunan Abi Dawud - Abu Hurairah; Ahmad bin Hanbal أحمد بن حنبل; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of the Jews greets you saying: Death may come upon you, reply: The same to you. Abu Dawud said: Malik b. ‘Adb Allah b. Dinar transmitted it in a similar manner, and al-Thawri transmitted it from ‘Abd Allah b. Dinar. He said in this version: The same to you.
Grade: Sahih

Hadith #5216 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
when he came near the mosque, he said to the Ansar; stand up showing respect to your chief.
Grade: Sahih

Hadith #5243 - Sunan Abi Dawud - Abu Hurairah; al-Laith bin Sa'd الليث بن سعد; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Isa bin Hammad bin Muslim, Zaghba عيسى بن حماد بن مسلم أبو موسى زغبة; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Prophet (ﷺ) said: In the morning alms are due from every bone in man’s fingers and toes. Salutation to everyone he meets is alms; enjoining good is alms; forbidding what is disreputable is alms; removing what is harmful from the road is alms; having sexual intercourse with his wife is alms. The people asked: He fulfils his desire, Messenger of Allah; is it alms? He replied: Tell me if he fulfilled his desire where he had no right, would he commit a sin ? He then said: Two rak’ahs which
Grade: Sahih

Hadith #5246 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Do not leave a fire burning in your houses while you are asleep.
Grade: Sahih

Hadith #5261 - Sunan Abi Dawud - Abu Hurairah; Isma'il bin Zakaria bin Mrh إسماعيل بن زكريا بن مرة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Abi Dawud)
Kill all the snakes except the little white one which looks like a silver wand. Abu Dawud said: A man said to me: A white snake does not wind in its movement. If it is correct, that is a sign in it, if Allah wills.
Grade: Da'if

Hadith #5262 - Sunan Abi Dawud - Abu Hurairah; Isma'il bin Zakaria bin Mrh إسماعيل بن زكريا بن مرة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Abi Dawud)
The Messenger of Allah (May peace be upon him) ordered a gecko to be killed, and calling it a noxious little creature.
Grade: Sahih

Hadith #5263 - Sunan Abi Dawud - Abdur Rahman bin Harmaz al-A'araj عبد الرحمن بن هرمز الأعرج أبو داود; Abu al-Zanad أبو الزناد; Abu Hurairah; al-Mughira bin 'Abdur Rahman - Qusayy المغيرة بن عبد الرحمن بن عبد الله - قصي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone kills a gecko with the first blow, such and such number of good deeds will be recorded for him, if he kills it with the second blow, such and such number of good deeds will be recorded for him less than the former; and if he kills it with the third blow, such and such number of good deeds will be recorded for him, less than the former.
Grade: Sahih

Hadith #5264 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Abi Dawud)
The Prophet (ﷺ) said: For the first blow seventy good deeds will be recorded.
Grade: Sahih

Hadith #5272 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sa'id bin Abi Sa'id; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
AbuUsayd heard the Messenger of Allah (ﷺ) say when he was coming out of the mosque, and men and women were mingled in the road: Draw back, for you must not walk in the middle of the road; keep to the sides of the road. Then women were keeping so close to the wall that their garments were rubbing against it.
Grade: Hasan